Neuroprotective effect of miR-519a-3p downregulation against sevoflurane-induced cognitive dysfunction via regulating ESR1 - Weiwei Lin; Dan Yu; Xiating Shi; Wanchao Liu (Toxicology and Applied Pharmacology, 2026)

Saccharomycopsis fibuligera solid-state fermentation of wheat bran for glutathione enrichment and functional improvement - Shu Jiang; Lin Zhou; Weiwei Dong; Jinshan Li; Yongmei Hu; Nan Peng; Shumiao Zhao (Food Research International, 2026)

Safety, immunogenicity, and broad-spectrum protective efficacy of a naturally attenuated GCRV-II strain against viral and bacterial challenges in grass carp - Dingzhe Zou; Yifei Li; Jie Zhou; Wangqian Xu; Ying Tian; Run Yang; Yujie Gu; Xiangyu Tian; Yucheng Lin; Jiping Zhang; Weiwei Zeng (Fish & Shellfish Immunology, 2026)

Co-optimization of cross-domain enhancement and frequency-domain decoupling: An engineering-oriented framework for underwater dam crack detection - Chuan Lin; Rongfeng Liu; Weiwei Lin; Rong Xiao; Yan Su (Engineering Structures, 2026)

High-temperature resistant homogeneous imidazolium functionalized poly (phthalazinone ether sulfone) anion exchange membranes for electrodialysis - Fanchen Sun; Qian Liu; Lin Zhuo; Xuefu Che; Peng Shi; Weiwei Kong; Yiping He; Hongyuan Lu; Lan Gong; Shouhai Zhang; Xigao Jian (Desalination, 2026)

Flash Joule heating enables defect and nitrogen configuration engineering in lignin-derived carbon for broadband electromagnetic wave absorption - Chenchen Wang; Jiayi Zhong; Chuanshuang Hu; Junda Yang; Yonghui Zhou; Weiwei Zhang; Jiangtao Xu; Xiuyi Lin (Chemical Engineering Journal, 2026)

Lactiplantibacillus plantarum LP15-1 alleviates deoxynivalenol-induced intestinal injury in mice by inhibiting ferroptosis and modulating the gut microbiota - Kunru Teng; Jiefeng Li; Beibei He; Dan Song; Tao Duan; Kuanbo Liu; Lin Qiao; Aike Li; Weiwei Wang; Shijie Fan (Toxicon, 2026)

PepOSX-AI: CPP - an interpretable transformer-based deep learning model for prediction of cell-penetrating peptides - Haowen Chen; Weiwei He; Kaiyan Feng; Rong Xu; Sheng Yin; Lin Zheng; Jing Chen; Mouming Zhao; Jucai Xu; Lijun You (Analytica Chimica Acta, 2026)

Sex-specific expression of detoxification proteins contributes to differential metabolic detoxification capacity and acaricide sensitivity in female and male Tetranychus cinnabarinus (Boisduval) - Sihan Chen; Weiwei Sun; Jiayan Duan; Ya Yang; Zhixin Jiang; Mingpeng Wang; Zhifeng Xu; Lin He; Kaiyang Feng (Pesticide Biochemistry and Physiology, 2026)

Experimental study of a dual-chain transmission hybrid power generation wave energy converter - Chenglong Li; Guojun Pan; Hui Li; Beichen Lin; Shaohui Yang; Weiwei Fan; Xianbin Yan (Ocean Engineering, 2026)

Sixteen-year dynamics of heavy metal(loid) pollution in agricultural soils of Zhejiang Province, China: Quantifying the contest between anthropogenic pressures and environmental investments - Weiwei Wang; Zhihui Fu; Linyan Xu; Jun Hu; Xiaozeng Miao; Liming Duan; Lingwen Wang; Yun Xia; Xiaohui Sun; Daohui Lin; Zhou Shi; Kun Yang (Journal of Hazardous Materials, 2026)

Comprehensive investigations reveal high occurrence of tet(X) in blaNDM-positive Acinetobacter spp. from Chinese cattle production systems - Weiwei Wang; Qing Wang; Yanhua Qiu; Guonian Dai; Bing Li; Honglin Lin; Yaxin Zhou; Jiyu Zhang (International Journal of Food Microbiology, 2026)

Wendan decoction ameliorates chronic obstructive pulmonary disease via regulating pulmonary microbiota homeostasis and inhibiting NOD-like receptor pyrin domain-containing 3-Caspase1 pathway: Integrating chemical profiling, efficacy validation and molecular mechanism elucidation - Song Lin; Qi Yu; Guoan Zhao; Xuanyu Fu; Yuyang Chen; Shutong Chen; Ying Lyu; Weiwei Jia; Yuran Sun; Wenbao Wang; Tianyang Wang; Yan Lin (Food Bioscience, 2026)

Corrigendum to “A biomimetic nanozyme enabling prolonged blood circulation for precise theranostics in hyperuricemia and gouty arthritis” [Manuscript Number: CEJ-D-25-56148] - Lujie Yu; Jian Zhang; Shutong Wu; Lin Chen; Qin Liu; Huifang Hao; Mingxin Zhao; Chunmei Jiang; Weiwei Zhang; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2026)

Computational discovery of HIF-1α/VHL protein–protein interaction inhibitors for hypoxic cell protection - Binglin Huang; Bijuan Lin; Xiao Chen; Yifan Zhu; Na Li; Bin Zheng; Weiwei Zheng; Xin Xue; Maobai Liu (Molecular Diversity, 2026)

Uncertainty-aware life cycle assessment of alternative urban water supply strategies with a case study of Hong Kong - Yu-yao Wang; Chok Hang Yeung; Pei Wang; Ziwei He; Weiwei Zhang; Chencheng Dong; Lin Lin; Xiao-yan Li (Sustainable Cities and Society, 2026)

Flexible radio-frequency carbon nanotube transistors operating in the sub-THz regime - Shuang Qian; Feifei Lin; Qianrui Zhou; Shujuan Liu; Weiwei Zhao; Qiang Zhao (Science Bulletin, 2026)

Rice 2C protein phosphatase, OsNY1, and magnesium oxide positively regulate arsenic tolerance by root cells reinforcement, metals detoxification, and protein phosphorylation - Zihang Lin; Lixia Sun; Weiwei Xia; Zhen Li; Fozia Ghouri; Muhammad Qasim Shahid (Journal of Hazardous Materials, 2026)

Online proteolysis and specific affinity enrichment of ACE inhibitory peptides on a magnetic nanoplatform from Torreya grandis protein - Kexin Liu; Jiajun Cui; Ke Xu; Jiaqi Zheng; Yixuan Xiao; Lin Chen; Sha Li; Jiyou Yang; Hongying Guo; Xin Wang; Fei Gao; Jie Li; et al. (Food Chemistry, 2026)

Immune dysregulation and cellular dysfunction mediate di-n-pentyl phthalate–induced hepatotoxicity: Insights from single-cell RNA sequencing - Yu Gan; Yongyi Luo; Xiandong Ye; Kaiyan Zhang; Zhenqiu Xia; Lei Yang; Chaoming Zhou; Gan Xie; Wenyan Zhong; Tengfei Yuan; Shuimiao Lin; Yuan Fang; et al. (Food and Chemical Toxicology, 2026)

Corrigendum to “a biomimetic nanozyme enabling prolonged blood circulation for precise theranostics in hyperuricemia and gouty arthritis” [Chem. Eng. J. 531 (2026) 173944] - Lujie Yu; Jian Zhang; Shutong Wu; Lin Chen; Qin Liu; Huifang Hao; Mingxin Zhao; Chunmei Jiang; Weiwei Zhang; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2026)

Developing a fusion algorithm based on UAV and mobile monitoring to quantify black carbon emissions from various types of planned straw residue burning - Jing Fu; Weiwei Chen; Chong Hui; Xue Yang; Lin Liang; Bowen Shi (Atmospheric Environment, 2026)

CYP4B1 inhibits lung adenocarcinoma metastasis by downregulating slug transcription via Sp1 - Sijia Wang; Yijie Liu; Yuan Yu; Shuwei Ren; Weiwei Lin; Kemeng Qiang; Haishan Huang; Honglei Jin (Clinical & Experimental Metastasis, 2026)

Hydrothermal zircon recording multi-stage tectonic reworking in Permian volcaniclastic rocks of the Emeishan Large Igneous Province, Southwest China - Junlang Chen; Xiaohong Liu; Tong Lin; Mingyou Feng; Hongming Tang; Jie Tan; Weiwei Wang; Junxin Shang; Tenglong Hu; Yili Zhao (Mineralogy and Petrology, 2026)

Ecological impacts of herbicide control in a protected coastal wetland of Chongming Island (Yangtze River Estuary, eastern China) assessed using macrobenthic indicators - Tian Zhu; Lin Yang; Hanzhong Liu; Shiyun Qiu; Qichen Jiang; Weiwei Lv; Yue Wang (Marine Pollution Bulletin, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Changes in drug resistance trend of Klebsiella pneumoniae in a teaching hospital in Zhejiang Province, 2005 – 2023 - Yulu Duan; Min Shen; Weiwei Zhang; Junda Zhou; Yueyang Xiao; Shanshan Deng; Xu Jia; Lin Zhang (Next Research, 2026)

In-situ heterojunction on high-aspect-ratio cellulose nanocrystals for long-range charge transport in e-skin - Chenchen Shen; Weiwei Chen; Lin Guo; Yanrui Zou; Shuan Han; Ning Yu; Lin Gan; Jin Huang (Carbohydrate Polymers, 2026)

The Spatial and Temporal Variability of the Clear Convective Boundary Layer at the ARM SGP Supersite - Yufei Chu; Zhien Wang; Min Deng; Guo Lin; Lulin Xue; Weiwei Li; Hyeyum Hailey Shin; Colby M. Brabec (Advances in Atmospheric Sciences, 2026)

Corrigendum to “Variations in soil fungal communities: Comparative insights from coniferous and mixed broadleaf-conifer forests” [Pedobiol. - J. Soil Ecol. 107 (2024) 151007] - Dexing Chen; Qiongyi Zhang; Siyu Chen; Yuqing Lin; Yuanming Zhu; Weiwei Sun; Mingjiu Chen; Shuangquan Zou; Xin Qian (Pedobiologia, 2026)

Underestimated small thermokarst lakes of the Qinghai-Tibet Plateau and their carbon emission potential - Xiaoqing Peng; Hengxing Luo; Weiwei Tian; Zhuoxuan Xia; Oliver W. Frauenfeld; Cuicui Mu; Lin Liu; Jing Luo; Lingcao Huang; Qinshan Zhao; Yimiao Yin (Global and Planetary Change, 2026)

Distinct mechanisms and sub-seasonal prediction of daytime, nighttime, and compound heatwaves in southern China: The role of intra-seasonal oscillations - Kaiqi Wang; Tuantuan Zhang; Song Yang; Fei Liu; Weiwei Wang; Wenshi Lin; Lianlian Xu; Yanheng Luo; Haiyang Xue (Atmospheric Research, 2026)

Taxonomy and Phylogeny of the Little-Known Ciliate Genus Cyclotrichium: With Special Reference to Two New Species - Zijun Cheng; Bowen Ye; Gang Li; Xiping Lian; Yehui Tan; Xiaofeng Lin; Weiwei Liu (Journal of Ocean University of China, 2026)

Improving growth performance across multiple sheep breeds by targeting the MSTN gene using an enhanced Cas12i system - Bo Liu; Huanyu Song; Miao Yan; Yu Wu; Pengfei Li; Zhanqing Fan; Yufei Chen; Yangsheng Wu; Jiapeng Lin; Liqin Wang; Xiaoyu Niu; Kun Xu; et al. (Science China Life Sciences, 2026)

An explainable machine learning model for accurate estimation of residual phthalate esters in Chinese agricultural soils - Weiwei Wang; Laigang Hu; Jialu Xu; Hongxia Zhu; Shuping Xing; Zhen Song; Yuchen Shen; Daohui Lin; Zhou Shi; Kun Yang (Journal of Hazardous Materials, 2026)

A transformer-reinforcement learning framework integrating acoustic thermometry for multi-pollutant prediction and control in a full-scale WtE plant in China - Yuxuan Ying; Linyi Chen; Hanqing Yang; Tianyi Zhu; Weiwei Cao; Zhenwei Yang; Hongyu Sun; Jinghao Ye; Yu Liu; Yunhua Zhao; Weiya Jin; Mi Yan; et al. (Journal of Cleaner Production, 2026)

A segment-based approach for global vertical adjustment of precipitable water vapor - Maijin Lin; Shaofeng Xie; Liangke Huang; Yifei Yang; Xiangping Chen; Xianghong Li; Weiwei Li; Lilong Liu (Advances in Space Research, 2026)

Local forcing of summer marine heatwaves in China's northern and eastern seas: Shortwave radiation and wind stress - Jingjing He; Xiaopei Lin; Xianyao Chen; Weiwei Ma (Limnology and Oceanography, 2026)
During the summer (June–August), marine heatwaves (MHWs) frequently occur in China's northern and eastern seas, including the Bohai Sea, Yellow Sea, and northern East China Sea. As a prominent marine environmental concern, these events have garnered widespread societal attention. However, the predictive capacity for such events remains constrained, underscoring the urgent need to comprehensively unravel the physical mechanisms governing their occurrence. In this study, we employ the Regional Ocean Modeling System to explore the local forcing factors driving MHW genesis. Our results reveal that the formation of summer MHWs is jointly determined by surface net heat fluxes, oceanic advection, and vertical mixing, with their relative contributions varying significantly across geographical locations. The formation of summer MHWs is closely related to surface wind stress anomalies. Under the background of weakened wind forcing, the temperature rise during the heat accumulation phase of MHWs is primarily driven by increased solar radiation, reduced cloud cover, and shoaling of the mixed layer. The suppression of vertical mixing further enhances heat accumulation in regions with water depth exceeding 50 m. These findings advance our understanding of the formation mechanisms of summer MHWs in China's northern and eastern seas, while improving the predictive capacity for such events.

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Prey selection and foraging behavior of Eriocheir sinensis towards three freshwater mollusk species: Mechanisms and ecological implications - Yanming Sui; Aijia Lin; Weiwei Su; Weiyi Zou; Yiyun Zhang; Linlan Lv; Hucheng Jiang (Behavioural Processes, 2026)

Size-dependent effects of polystyrene Nanoplastics on hepatic Immunometabolism and the gut-liver Axis in the Swamp Eel (Monopterus albus) - Mingming Han; Wenzong Zhou; Ji Liang; Aileen Tan Shau-Hwai; Zihan Zhou; Lin Cheng; Jiayuan Liao; Weiwei Huang; Qichen Jiang; Weiwei Lv (Aquaculture, 2026)

Precipitation dominates remote lake primary productivity: A Holocene perspective based on regional synthesis from northeastern Asia - Dongliang Ning; Xianqiang Meng; Qi Lin; Enfeng Liu; Zhenyu Ni; Weiwei Sun; Wenfang Zhang; Yao Wang; Rong Chen; Enlou Zhang (Quaternary Science Reviews, 2026)

Underwater topography regulates the relationship between water depth and sedimentary n-alkane distributions in lakes - Durui Lin; Enlou Zhang; Weiwei Sun; Xianqiang Meng; Zhenyu Ni; Yao Wang (Quaternary Science Reviews, 2026)

Experimental and numerical research on thermal characteristics and ampacity of multi-layer wound non-metallic armoured optoelectronic cable winch system in Oceanographic Research Vessel - Wenhua Li; Yujie Zhang; Shanying Lin; Gen Li; Weiwei Shen (Ocean Engineering, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Hydrological changes accelerate ecological degradation in a subtropical floodplain lake: A multi-proxy sedimentary record highlights the restoration potential of river-lake connectivity - Yanxian Wei; Weiwei Sun; Yanjie Zhao; Durui Lin; Enlou Zhang (Journal of Environmental Management, 2026)

Essential oil-based intelligent packaging with controlled release: A review on mechanisms, encapsulation, and molecular interactions - Yinuo Zhou; Xianting Yun; Weiwei Lin; Haohao Shi; Zhaojie Li; Yonghuan Yun; Meizhen Xie; Lipin Chen (Food Chemistry, 2026)

Combining protein fibrosis with dynamic non-covalent crosslink to improve the mechanical properties of high internal phase emulsion and its application in hollow model printing - Mengjia Guo; Xiaoxiao Hong; Jiawang Shi; Zhiqian Lin; Huajun Jian; Yu Cheng; Minhao Xie; Weiwei Li (Food Hydrocolloids, 2026)

A biomimetic nanozyme enabling prolonged blood circulation for precise theranostics in hyperuricemia and gouty arthritis - Lujie Yu; Jian Zhang; Shutong Wu; Lin Chen; Qin Liu; Huifang Hao; Mingxin Zhao; Chunmei Jiang; Weiwei Zhang; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2026)

Epidemiological characteristics of Chlamydial infection in hospitalized children in China: A nationwide retrospective study - Huiwen Zheng; Xinyu Wang; Xirong Wu; Yajie Guo; Feina Li; Jing Xiao; Hui Qi; Weiwei Jiao; Guoshuang Feng; Ju Yin; Lin Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Differences in Habitat Substrate Preference Selection Among Sexes and Populations of Leptobotia elongata - Lixiong Yu; Min Wang; Jiaxin Li; Fengyue Zhu; Yuliang Yuan; Huiwu Tian; Mingdian Liu; Weiwei Dong; Ji Yang; Senfan Ke; Chenyu Lin; Xinbin Duan (Fishes, 2026)
Cascade hydropower development in the upper Yangtze River has substantially altered riverine habitat conditions. However, quantitative information on fish substrate preferences remains limited. Based on field surveys, six representative substrate types were identified in the Yibin and Jiangjin reaches, and substrate selection patterns of Leptobotia elongata were quantified under controlled flume conditions. This study examined sex-specific and population-level differences in substrate preference. A total of 50 samples were analyzed using one-way ANOVA and the Kolmogorov–Smirnov test. The results are summarized as follows: (1) Substrates of 40–20 mm: Individual female L. elongata exhibited the longest residence time on the 40 mm substrate (1640 s), while individual males also spent the longest time on the 40 mm substrate (1549 s). Within this substrate range, males showed a preference only for the 40 mm substrate (PR = 739), whereas females preferred three substrate types, with the strongest preference for the 40 mm substrate (PR = 7543). (2) Substrates of 10–2.5 mm: Female individuals spent the longest time on the 10 mm substrate (1468 s), and male individuals likewise showed the longest residence time on the 10 mm substrate (1568 s). In this range, males did not show a significant preference for any substrate (PR = −907), whereas females preferred three substrate types, with the 2.5 mm substrate exhibiting the highest preference intensity (PR = 2059). (3) Population-level patterns for 40–20 mm substrates: The population spent the longest time on the 40 mm substrate (1799 s) and preferred three substrate types, among which the 20 mm substrate had the highest preference ratio relative to the other preferred substrates (PR = 4750). (4) Population-level patterns for 10–2.5 mm substrates: The longest residence time was observed on the 10 mm substrate (1762 s). The population preferred three substrate types, with the 10 mm substrate showing the highest preference ratio (PR = 5709). Overall, L. elongata showed a general tendency to prefer larger-sized substrates. This preference is likely associated with enhanced habitat complexity, improved foraging opportunities, and the formation of low-velocity refuges. Our results suggest that maintaining or restoring coarse substrate patches in regulated reaches may improve habitat suitability for L. elongata and potentially benefit other benthic fishes with similar ecological requirements.

Reversible brain functional alterations induced by Short-Term high altitude exposure - Xinjuan Zhang; Weiwei Xie; Cunxiu Fan; Yanqiu Liu; Yuan Wang; Danlu Chen; Yuhua Zhao; Wu Yin; Haipeng Liu; Jianzhong Lin; Jiaxing Zhang (Brain Imaging and Behavior, 2026)

Moisture-resistant Al-based MOF with helical SBUs for efficient CO2 adsorption, separation and desorption - Laigang Hu; Weiwei Wang; Ling Jiang; Jinru Hu; Hongxia Zhu; Mengxue Zhang; Jian Wu; Daohui Lin; Kun Yang (Chemical Engineering Journal, 2026)

Atmospheric Submicron Aerosols Over the Tibetan Plateau: A Review - Lin Liang; Wenhui Zhao; Xiaomin Chen; Weiwei Hu; Pengfei Yu; Shan Huang (Current Pollution Reports, 2026)

A modeling approach for dynamically assessing the carbon storage potential of the Manila clam Ruditapes philippinarum in typical aquaculture systems - Weiwei Jiang; Weiwei Li; Fan Lin; Jinghui Fang; Yuze Mao; Jianguang Fang; Zengjie Jiang (Aquaculture, 2026)

Molecular identification and population genetic analysis of a three-way cross hybrid abalone - Haichen Zhang; Qizhen Xiao; Weihong Lin; Zekun Huang; Benben Miao; Yang Gan; Chengyun Li; Caihuan Ke; Xuan Luo; Weiwei You (Aquaculture, 2026)

Aerosol-cloud layer detection algorithm of the DQ-1/ACDL - Feiyue Mao; Weiwei Xu; Zengxin Pan; Lin Zang; Ge Han; Linxin Dai; Xiuqing Hu; Weibiao Chen; Wei Gong (Remote Sensing of Environment, 2026)

Recent advances in formaldehyde adsorption by metal–organic frameworks for indoor air filtration - Andrea Hoe; Hanjie Lin; Bing Guo; Yeqing Wang; Weiwei Zheng; Jianshun Zhang (Journal of Hazardous Materials, 2026)

Molten Li/Na/K ternary carbonate salt pyrolysis of biomass: A facile approach for co-production of porous biochar, CO-enriched syngas, and high-selectivity bio-oil - Jiazhen Tang; Tianyu Lu; Xing Xie; Dan Lin; Dongjing Liu; Qingfa Zhang; Mingfeng Wang; Weiwei Liu; Zhong Ma; Haiping Yang; Shihong Zhang; Bin Li (Journal of Cleaner Production, 2026)

A CFD–DEM model for simulating mechanical responses of saturated paddy soil: model development and experimental verification - He Zheng; Weiwei Duan; Ziqi Li; Yejun Zhu; Dongfang Li; Ze Liu; Wenxiang Xu; Maohua Xiao; Lin Zhu (Computers and Electronics in Agriculture, 2025)

Impact of temperature fluctuation on biofilm formation and removal of different Listeria monocytogenes strains in ice cream processing environments - Zhao Li; Jiangtian Wang; Yifan Gao; Hongzhi Zhang; Yangtai Liu; Xuejuan Xia; Weiwei Li; Lin Yan; Qingli Dong (Food Research International, 2025)

Seismic performance of a low yield point steel link with corrugated web for RC double-column bridge bent - Sidong Feng; Jun He; Wei Fan; Weiwei Lin; George Vasdravellis (Engineering Structures, 2025)

Charcoal-derived hard carbon anodes with enhanced sodium storage performance for sodium-ion batteries - Shengchen Yang; Yan Li; Chun Chen; Hui Wang; Kaihang Wang; Qingqing Li; Ruize Dong; Manman Chen; Cai Zhao; Weiwei Xu; Lin Sun; Tao Zhang; et al. (Chemical Engineering Journal, 2025)

Optimizing MERRA-2 aerosol extinction coefficient by fusing CALIPSO and SAGE observations with machine learning - Jingru Yang; Lin Zang; Feiyue Mao; Yi Zhang; Weiwei Xu; Fan Liu; Tingting Liu (Atmospheric Environment, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

A comprehensive study on coastline mapping and sustainable management of coastal resources in China: Connotation, methodologies, and practical applications - Weiwei Dong; Guilan Lin; Yongling Zheng; Huiquan Lu; Chengqiang Wu; Jingjing Bao (Journal of Coastal Conservation, 2025)

Advanced design principles for wireless ingestible capsules towards gastrointestinal health monitoring - Feifei Lin; Heming Xu; Weiwei Zhao; Shujuan Liu; Qiang Zhao (Science Bulletin, 2025)

Numerical acceleration method for static and dynamic analysis of deepwater laying pipelines - Pu Xu; Jixiang Zheng; Weiwei Lin; Yiming Hu; Naiquan Ye (Ocean Engineering, 2025)

Revealing the characteristic honey-like aroma formation in honey-scented black tea via molecular sensory analysis - Peng Zhang; Weiwei Wu; Bangxing Ma; Changkun Zheng; Qi Lin; Xinyi Zhao; Yan Huang; Fuming Lin; Weijiang Sun (Food Chemistry, 2025)

Dissecting the role of foulant-spacer interaction energy on membrane fouling with a collision-attachment-based Monte Carlo approach - Junxia Liu; Mingxin Peng; Bingzhi Liu; Wei Fu; Chenxi Lin; Zhiwei Tang; Dongsheng Zhao; Weiwei Huang; Tian Li (Desalination, 2025)

Etiological characteristics of Mycoplasma pneumoniae infection and macrolide resistance in children in beijing: a retrospective study from 2018 to 2024 - Wanning Chen; Hui Qi; Weiwei Jiao; Yajie Guo; Yuqing Wang; Jinrong Liu; Baoping Xu; Chengsong Zhao; Lin Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Response and evaluation of polyploidy induction on morphology, physiology and drought tolerance of Hydrangea paniculata ‘Pink Diamond’ - Shizhen Cai; Xingyi Lin; WeiWei Zhou; Shiyuan Xu; Shuju Huang (Euphytica, 2025)

Comparative analysis of feed efficiency in Pacific abalone and its hybrid under varied environmental conditions - Wenchao Yu; Ziheng Yin; Yuehan Yan; Lin Cong; Miaoqin Huang; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture International, 2025)

CPK12 decodes effector-triggered calcium signaling and phosphorylates PIP2;1 to facilitate apoplastic ROS transport into the cytoplasm in Arabidopsis - Zhiyi Jia; Weiwei Yu; Xijie Guo; Jianwei Li; Fan Qi; Yayun Zhu; Xinzhong Cai; Xiaoting Li; Ning Li; Hansong Dong; Fucheng Lin; Yan Liang (Molecular Plant, 2025)

Ceramic fiber aerogels based flexible solar steam generators enabling efficient thermal localization and high salt resistance - Yun Jiang; Yumin Liu; Lin Li; Zhibin Li; Pengzhang Li; Xianshu Qiao; Wenyan Zhao; Chuanjin Tian; Weiwei Sun; Yanhao Dong; Zhipeng Xie; Chang-An Wang (Desalination, 2025)

Natural fluvial connection across watersheds - Xiwei Guo; Anastasia Piliouras; Peirong Lin; Weiwei Yao (Earth-Science Reviews, 2025)

Prediction of asphalt rheological properties for paving and maintenance assistance using explainable machine learning - Fan Zhang; Augusto Cannone Falchetto; Di Wang; Zhenkun Li; Yuxuan Sun; Weiwei Lin (Fuel, 2025)

Influence of N2 and CO2 dilution on methane MILD combustion: Insights into temperature distribution and emission optimization - Junjian Tian; Yue Ma; Weiwei Song; Zhanshi Ni; Xiang Liu; Peng Hu; Kesheng Meng; Qizhao Lin (Fuel, 2025)

Asymmetric gradient-structured PPy@bacterial nanocellulose aerogels enable broadband microwave absorption via synergistic polarization-conduction loss - Xi Lin; Chenchen Wang; Chaoqun Zhang; Qi Guo; Chuanshuang Hu; Yi Yang; Yonghui Zhou; Xiuyi Lin; Weiwei Zhang; Jiangtao Xu (Chemical Engineering Journal, 2025)

Cellulose nanocrystal-modified hydrogel wearable sensor with self-healing function from dynamic bond and controllable dual hydrogen-bond crosslinking - Ruihuan Gu; Weiwei Chen; Yanrui Zou; Tingting Yang; Zirui Liu; Ning Yu; Jin Huang; Lin Gan (Carbohydrate Polymers, 2025)

Red mud amendments reduce cadmium mobility in paddy soil and limit cadmium accumulation in rice grains: A mechanistic investigation - Jiali Yan; Xuwei Li; Jintao Li; Jiankang Zhou; Jiamin Shi; Kangfu Liu; Xin Chen; Shiqi Zhou; Weiwei Sun; Fuqing Sui; Xiaochen Lin; Lei Zhang; et al. (Plant and Soil, 2025)

Synthesis of ZIF-8 Coated MnO2 Functionalized Antibacterial Peptide Nanoparticles and Its Antibacterial and Wound-Healing Promotion Studies - Mengzhu Xiao; Yujia Wu; Wanzhen Li; Jun Wang; Weiwei Zhang; Lin Gui; Fei Ge (Current Microbiology, 2025)

Evaluating the sustainability potential of perennial rice in southeastern China by comparing yield, environmental impacts and economic benefits - Hailong Xu; Bianhong Zhang; Bin Qin; Jinying Li; Chaojie Lan; Jingnan Zou; Yazhou Liu; Chunlin Guo; Zhimin Lin; Qiaohong Fan; Changxun Fang; Zhixing Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

NaOH-assisted heat curing towards highly permeable, superior selective, and antifouling TFC nanofiltration membranes - Weiwei Huang; Xiaozhen Lu; Wenzong Zhou; Weiwei Lv; Quan Yuan; Hang Yang; Xinwei Kang; Daoji Wu; Lin Wang; Xuewu Zhu (Desalination, 2025)

Experimental and Numerical Study on the Temperature Rise Characteristics of Multi-Layer Winding Non-Metallic Armored Optoelectronic Cable - Shanying Lin; Xihong Kuang; Yujie Zhang; Gen Li; Wenhua Li; Weiwei Shen (Journal of Marine Science and Engineering, 2025)
The non-metallic armored optoelectronic cable (NAOC) serves as a critical component in deep-sea scientific winch systems. Due to its low density and excellent corrosion resistance, it has been widely adopted in marine exploration. However, as the operational water depth increases, the NAOC is subjected to multi-layer winding on the drum, resulting in a cumulative temperature rise that can severely impair insulation performance and compromise the safety of deep-sea operations. To address this issue, this paper conducts temperature rise experiments on NAOCs using a distributed temperature sensing test rig to investigate the effects of the number of winding layers and current amplitude on their temperature rise characteristics. Based on the experimental results, an electromagnetic thermal multi-physics field coupling simulation model is established to further examine the influence of these factors on the maximum operation time of the NAOC. Finally, a multi-variable predictive model for maximum operation time is developed, incorporating current amplitude, the number of winding layers, and ambient temperature, with a fitting accuracy of 97.92%. This research provides theoretical and technical support for ensuring the safety of deep-sea scientific operations and improving the reliability of deep-sea equipment.

Genetic and metabolic signatures of blooming-stage tea flowers in novel albino cultivars: Implications for functional food development - Shanshan Zeng; Xiansheng Liao; Zheng Liu; Feng Liu; Wenjing Gui; Weiwei Ren; Hongzheng Lin; Yucheng Zheng; Naixing Ye (Food Bioscience, 2025)

GWAS and GS analysis revealed the selection and prediction efficiency for yield, plant morphological, and fiber quality in Gossypium barbadense - Tao Yang; Honggang Wang; Jikun Song; Kang Zhao; Bo Pang; Yongpan Wang; Ping Luo; Weiwei Liang; Shunyu Shi; Jie Wang; Yifeng Lin; Jing Li; et al. (Theoretical and Applied Genetics, 2025)

A Deep Learning Framework for Parameter Estimation in 1D Marine Ecosystem Model - Ao Li; Kewei Zhao; Weiwei Fang; Chan Shu; Runjie Zhou; Qiuyi Li; Xiaolong Huang; Xiaohong Lei; Menghan Xu; Haoyu Jiang; Lin Mu (Journal of Marine Science and Engineering, 2025)
Marine ecosystems play an increasingly critical role in both global climate regulation and the impacts of anthropogenic activities. Accurate marine biogeochemical numerical models are essential tools for understanding and predicting the complex dynamics of these systems. However, as model complexity increases, so does the number of biological parameters and the uncertainties associated with them, which can substantially affect model performance. Consequently, efficient and reliable parameter estimation has become a key challenge in model development and application. In this study, we proposed a deep learning-based approach for parameter estimation in numerical models, utilizing deep neural networks to capture the complex nonlinear relationships between numerical model input parameters and output variables. A one-dimensional marine ecosystem model is employed as a case study to evaluate the effectiveness of the proposed method. The results demonstrate that (1) the deep learning approach provides an automated and adaptive solution for parameter estimation, significantly improving the efficiency of model calibration in engineering and scientific applications by enabling rapid identification of near-optimal parameter sets; and (2) the deep learning model effectively learns the underlying nonlinear mappings between inputs and outputs. During training, the mean squared error (MSE) loss exhibits a steady decline, with minor fluctuations in the early stages, ultimately converging to a stable value. The predicted parameter combinations show strong agreement with the reference numerical model outputs, yielding correlation coefficients exceeding 0.95.

Comparison of PAH mass emissions and their toxicity-weighted trends in China, 2000–2022 - Weiwei Wang; Laigang Hu; Lu Chen; Xiaozeng Miao; Wenhao Wu; Zhou Shi; Daohui Lin; Kun Yang (Science of The Total Environment, 2025)

Impacts of changes in PM2.5 concentrations and their major components on blood pressure during pregnancy - Peiyao Chen; Wenjie He; Yan Jin; Xueting Liu; Qiannan Wei; Jianling Shen; Qingqing Wang; Li Wen; Lijie Wang; Qing Wei; Qiansheng Hu; Weiwei Lin (Journal of Hazardous Materials, 2025)

Interactions of nematodes and ammonia-oxidizing bacteria mediate nitrification in two contrasting soils - Qing Wan; Lin Chen; Jianming Xu; Donghao Ma; Wei Li; Shixiu Zhang; Yong Li; Weiwei Jin; Jiabao Zhang (Journal of Environmental Management, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Identifying Novel QTLs and Candidate Genes for Tillering Ability in Sugarcane (Saccharum spp.) - Junteng Fang; Ruiqiang Lai; Zaid Chachar; Yiyun Gui; Lina Fan; Huanzhang Lin; Weijun Cai; Yueping Su; Weiwei Chen; Xiaoming Xue; Yucong Li; Liping Xu; et al. (Sugar Tech, 2025)

Construction of a highly sensitive recoverable lipase@sodium alginate/cyclodextrin/graphene oxide film for triglyceride detection in dairy products - Qi Ao; Ziran Chen; Lin Jiang; Weiwei Jin (Chemical Engineering Journal, 2025)

Correction to: Sacubitril/valsartan attenuated myocardial inflammation, fibrosis, apoptosis and promoted autophagy in doxorubicin-induced cardiotoxicity mice via regulating the AMPKα–mTORC1 signaling pathway - Feng Hu; Senbo Yan; Li Lin; Xiaoxia Qiu; Xinghe Lin; Weiwei Wang (Molecular and Cellular Biochemistry, 2025)

An innovative high-rate biofilm-based process: Biopolymer production and recovery from wastewater organic pollutants - Haifeng Zhang; Yi Zhang; Lin Li; Shujuan Huang; Weiwei Ma; Boyan Xu; How Yong Ng; Dong-Hoon Kim; Seoktae Kang; Xueqing Shi (Journal of Environmental Management, 2025)

The differences in thermal physiological parameters, thermal comfort, and thermal acceptability under the same thermal sensation in air-conditioned environments between winter and summer - Weiwei Liu; Shan Li; Diyu Yang; Jun Xu; Liangliang Sun; Weibin Lin (Energy and Buildings, 2025)

The involvement of auxin response factor OsARF7 in positively regulating root development by mediating the expression of OsCRL1 in rice (Oryza sativa L.) - Congying Sun; Kai Fan; Xin Wang; Honghai Liu; Nuoping Guo; Wanyu Liu; Guixiang Ye; Weiwei Lin; Wenxiong Lin; Zhaowei Li (Plant Molecular Biology, 2025)

Design of impact ultrasonic penetrator and optimization of impact efficiency - Yinchao Wang; Ziming Yu; Zihao Yin; Weiwei Zhang; Lin Zu; Guanghong Tao; Suyang Yu (Advances in Space Research, 2025)

Effects of mixed exposure to PFAS on adolescent non-alcoholic fatty liver disease: Integrating evidence from human cohorts, toxicogenomics, and animal models to uncover mechanisms and potential target sites - Xiushuai Du; Dan-Lin Li; Xueming Xu; Yitian Wu; Zhiyuan Du; Gang Liang; Yue-Zu Li; Ya-Jie Zheng; Yu Qin; Kelei Qian; Jing Xu; Liping Gao; et al. (Journal of Hazardous Materials, 2025)

Sacubitril/valsartan attenuated myocardial inflammation, fibrosis, apoptosis and promoted autophagy in doxorubicin-induced cardiotoxicity mice via regulating the AMPKα–mTORC1 signaling pathway - Feng Hu; Senbo Yan; Li Lin; Xiaoxia Qiu; Xinghe Lin; Weiwei Wang (Molecular and Cellular Biochemistry, 2025)

An integrated immunofluorescent detection system for automated and sensitive protein quantification based on a microfluidic flow cytometry platform - Lin Cheng; Yitong Li; Weiwei Ji; Jing Yan (Analytica Chimica Acta, 2025)

Synthesis of 3- and 5-β-anhydroicaritine norcantharidin conjugates - Han Lin; Weiwei Dong; Changkuo Zhao; Xianheng Wang (Natural Product Research, 2025)

Rapid Video Analysis for Contraction Synchrony of Human Induced Pluripotent Stem Cells-Derived Cardiac Tissues - Yuqing Jiang; Mingcheng Xue; Lu Ou; Huiquan Wu; Jianhui Yang; Wangzihan Zhang; Zhuomin Zhou; Qiang Gao; Bin Lin; Weiwei Kong; Songyue Chen; Daoheng Sun (Tissue Engineering and Regenerative Medicine, 2025)

Fatigue behavior of square steel strut-to-gusset plate welded connections under eccentric compression: Full-scale and reduced-scale tests - Xiaoqing Xu; Hongfa Luo; Bin Wang; Yuqing Liu; Kaixiang Miao; Rui Hao; Weiwei Lin; Yuwen Zhou; Dongyang He; Md Asadujjaman (Engineering Structures, 2025)

Experimental study on shear mechanism of a new TU-type connector at HSS-UHPC interface - Yangqing Liu; Yibo Zhao; Haiyan Yang; Xiaoqing Xu; Weiwei Lin; Xiaoqing Du; Yuqing Liu (Engineering Structures, 2025)

A simple and effective low-temperature pyrolysis control strategy to enhance the sodium storage performance of lignite-based carbon materials - Yongjia Lin; Jianbo Jia; Jing Wang; Xinru Kang; Guangxu Huang; Baolin Xing; Weiwei Kang; Chuanxiang Zhang (Chemical Engineering Journal, 2025)

Enhancing electromechanical conversion and motion-monitoring application of pore-oriented cellulose nanocrystal/agarose aerogel modified with flexible heterojunction structures - Weiwei Chen; Lin Gan; Jie Xiong; Ga Liu; Tingting Yang; Yanrui Zou; Zhicheng Zhang; Jin Huang (Carbohydrate Polymers, 2025)

Performance verification of GNSS/5G tightly coupled fusion positioning in urban occluded environments with a smartphone - Weiwei Song; Haijuan Ding; Laihong Zhang; Liang Chen; Wenfei Guo; Wei Lin; Shufeng Qi (GPS Solutions, 2025)

The source, transport, deposition and direct radiative effect of mineral dust over western China: A modeling study of July 2022 with focus on the Tibetan Plateau - Lin Liang; Zhiwei Han; Weiwei Chen; Jiawei Li; Mingjie Liang; Shujing Shen (Atmospheric Research, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Study on susceptibility differences of Tetranychus cinnabarinus (Boisduval) males and females to acaricides - Weiwei Sun; Sihan Chen; Lei Liu; Zhixin Jiang; Kaiyang Feng; Lin He (Pesticide Biochemistry and Physiology, 2024)

Variations in soil fungal communities: Comparative insights from coniferous and mixed broadleaf-conifer forests - Dexing Chen; Qiongyi Zhang; Siyu Chen; Yuqing Lin; Yuanming Zhu; Weiwei Sun; Mingjiu Chen; Shuangquan Zou; Xin Qian (Pedobiologia, 2024)

Simple theranostics nanoagent for precision suppression of tumor growth and metastasis: A traditional fermented product having a novel functional breakthrough - Pengmin Liu; Rong Dai; Juan Li; Lin Chen; Qi Liu; Yuhang Wang; Shichao Meng; Binyue Zhang; Jinxuan Li; Weiwei Kang; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2024)

A novel Al-based MOF with straight channel and pocket pore structure for trace benzene adsorption and benzene/cyclohexane separation - Laigang Hu; Weiwei Wang; Xiaozeng Miao; Min Hu; Dong Luo; Wenhao Wu; Daohui Lin; Kun Yang (Chemical Engineering Journal, 2024)

The influences of ApoE isoforms on endothelial adherens junctions and actin cytoskeleton responding to mCRP - Zhengrong Zhang; Weiwei Lin; Qini Gan; Maohua Lei; Bin Gong; Chao Zhang; Jessica Salles Henrique; Jingyan Han; Hua Tian; Qiushan Tao; Lawrence A. Potempa; Thor D. Stein; et al. (Angiogenesis, 2024)

Relevance of genetic causes and environmental adaptation of Cronobacter spp. isolated from infant and follow-up formula production factories and retailed products in China: A 7-year period of continuous surveillance based on genome-wide analysis - Wei Tong; Dajin Yang; Shaofu Qiu; Sai Tian; Zehong Ye; Shuran Yang; Lin Yan; Weiwei Li; Ning Li; Xiaoyan Pei; Zhongqing Sun; Chengwei Liu; et al. (Science of The Total Environment, 2024)

Human impacts overwhelmed climate as the dominant factor controlling lacustrine organic matter accumulation in Erhai Lake 2000 years ago, Southwest China - Durui Lin; Enlou Zhang; Enfeng Liu; Weiwei Sun; Rong Wang; Xianqiang Meng; Zhenyu Ni; Yao Wang; Yang You (Science of The Total Environment, 2024)

Characterization of volatile compounds and identification of key aroma compounds in different aroma types of Rougui Wuyi rock tea - Yilin Liang; Zhihui Wang; Lingzhi Zhang; Haomin Dai; Weiwei Wu; Zhiqiang Zheng; Fuming Lin; Jie Xu; Yan Huang; Weijiang Sun (Food Chemistry, 2024)

Local defect structure design enhanced energy storage performance in lead-free antiferroelectric ceramics - Peixuan Li; Simin Wang; Jin Qian; Guanglong Ge; Luomeng Tang; Jinfeng Lin; Weiwei Yang; Jimin Lin; Weikang Lin; Bo Shen; Jiwei Zhai (Chemical Engineering Journal, 2024)

First wetland mapping at 10-m spatial resolution in South America using multi-source and multi-feature remote sensing data - Weiwei Sun; Gang Yang; Yuling Huang; Dehua Mao; Ke Huang; Lin Zhu; Xiangchao Meng; Tian Feng; Chao Chen; Yong Ge (Science China Earth Sciences, 2024)

Silicon balance in an integrated multi-tropical aquaculture ecosystem, Sanggou Bay, China - Ruihuan Li; Zengjie Jiang; Fan Lin; Yitao Zhang; Weixin Wang; Kai Zhang; Weiwei Li; Dongjie Wan; Yazhou Shi (Frontiers in Marine Science, 2024)
Farmed aquaculture species play an important role in regulating nutrient cycles in farming systems. Compared with nitrogen and phosphorus, the role of farmed species in the silicon (Si) cycle remains poorly understood. To help reduce this uncertainty, we clarified the sources and sinks of silicate and quantified the Si pools in an aquaculture system in Sanggou Bay (SGB). The results showed that dissolved inorganic nutrient levels were significantly lower during the dry season than during the wet. Dissolved silicate (DSi) is a potential limiting factor for phytoplankton growth during spring, and phosphorus limitation occurs during summer. The budget results indicated that large amounts of nitrogen, phosphate (DIP), and DSi were buried in the sediment or transformed into other forms during both the wet and dry seasons. The nitrogen and DIP cycles were strongly influenced by bivalve excretion and farmed species harvesting; however, these processes had little impact on the Si cycle. Si availability depends on both external inputs and internal recycling. DSi was primarily supplied from the Yellow Sea, with a minor contribution from the river due to river discharge during spring. However, during summer, riverine inflow (accounting for 83% of the total influx) was the major DSi source followed by benthic flux (12%). Biogenic silica (BSi) burial efficiency in the sediment was estimated to be 78% during spring and 23% during summer. The BSi preservation efficiency in bivalves during spring was high (53%), leading to a higher Si retention than in river discharge. Bivalves biodeposition plays an important role in the Si burial process. We suggest that this high retention is essentially controlled by the biodeposition mechanism, which is directly controlled by the exotic suspension feeders. Bivalves have the potential to alter Si retention in the bay by producing large amounts of biodeposits and accelerating the silica cycle, which may lead to more carbon dioxide being absorbed by diatoms.

Unveiling the impacts of salts on halotolerant bacteria during filtration: A new perspective on membrane biofouling formation in MBR treating high-saline organic wastewater - Haiyang Lin; Yucai Du; Mengchao Yu; Wenyue Zhang; Weiwei Cai (Chemosphere, 2024)

The effect of different drying temperatures on flavonoid glycosides in white tea: A targeted metabolomics, molecular docking, and simulated reaction study - Zhihui Wang; Yilin Liang; Weiwei Wu; Chenxi Gao; Chunyan Xiao; Zhe Zhou; Fuming Lin; Weijiang Sun (Food Research International, 2024)

Single-cell characterization of major components of plant cell walls in situ by Raman spectroscopy - Yujian Li; Weiwei Shen; Xi Zhang; Yaning Cui; Yuanyuan Zhao; Yayu Guo; Xiaojuan Li; Shuizhong Wang; Guoyong Song; Pu Wang; Jianfeng Ma; Jinxing Lin (Science China Life Sciences, 2024)

Soat2 inhibitor avasimibe alleviates acute pancreatitis by suppressing acinar cell ferroptosis - Weiwei Luo; Lin Chen; Hui Sun; Siqin Zhang; Xiaowu Dong; Jiajia Pan; Weiming Xiao; Guotao Lu; Yaodong Wang; Hongwei Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Prediction of Pier Scour Depth under Extreme Typhoon Storm Tide - Zongyu Li; Weiwei Lin; Dongdong Chu; Feng Liu; Zhilin Sun; Wankang Yang; Hanming Huang; Dan Xu (Journal of Marine Science and Engineering, 2024)
The Western Pacific region is highly vulnerable to typhoon storm surge disasters, with localized erosion posing a particularly prominent issue for coastal marine structures. The prevalence of extreme typhoon storm surges poses a significant threat to the safety of engineering projects in these areas. In this study, a parameterized wind field model with precise calculation of wind speed was employed to establish a numerical model for typhoon storm tides. Based on the Western Pacific typhoon data from 1949 to 2023, hydraulic simulations were conducted for Hangzhou Bay, Xiangshan Port, and Yueqing Bay, revealing maximum flow velocities of 4.5 m/s, 1.95 m/s, and 2.09 m/s, respectively. These velocities exceeded the maximum possible tidal flow by 0.47–1.17 m/s. Additionally, using Sun’s velocity formula, the initiation flow velocities were calculated to be 1.85 m/s, 1.81 m/s, and 2.06 m/s for the aforementioned locations. Through localized erosion tests conducted around typical bridge piers and the subsequent application of similarity criteria, the maximum depth of localized erosion in the study area was determined to range from 2.16 m to 16.1 m, which corresponds to 1.1–2.3 times the scour caused by the maximum tidal flow scenario. A comparison of the erosion test results with calculations based on several formulas demonstrated that the scour prediction formula proposed by Sun exhibited the highest accuracy. This study supplements the understanding of the impact of typhoon storm surges on bridge pier erosion and provides a scientific basis for the design of bridge foundations.

The association between PM2.5 components and blood pressure changes in late pregnancy: A combined analysis of traditional and machine learning models - Lijie Wang; Li Wen; Jianling Shen; Yi Wang; Qiannan Wei; Wenjie He; Xueting Liu; Peiyao Chen; Yan Jin; Dingli Yue; Yuhong Zhai; Huiying Mai; et al. (Environmental Research, 2024)

Association of NID2 SNPs with Glioma Risk and Prognosis in the Chinese Population - Jie Hao; Congmei Huang; Weiwei Zhao; Lin Zhao; Xiuxia Hu; WenJie Zhang; Le Guo; Xia Dou; Tianbo Jin; Mingjun Hu (NeuroMolecular Medicine, 2024)

Source-Specific Ecological Risk of Atmospheric PM2.5-Bound Metals and Implications for Air Pollution Control: A Regional Perspective from China - Weiwei Lin; Hedi Zhang; Yuming Lai; Shuling Zhuang; Qiannan Wei; Shaojie Fu; Dejian Mai; Luan Yuan; Qing Wei; Dingli Yue; Qiansheng Hu (Exposure and Health, 2024)

Popcorn-like bimetallic palladium/platinum exhibiting enhanced peroxidase-like activity for signal enhancement in lateral flow immunoassay - Qianqian Cao; Yiqin Liu; Lin Yang; Ting Tan; Jian He; Weiwei Chen; Ranhui Li; Weiguo Wang (Analytica Chimica Acta, 2024)

Numerical Study on Electromagnetic Thermal Performance of Non-Metallic Armoured Optoelectronic Cable Winch System - Wenhua Li; Huaizhao Wu; Shanying Lin; Weiwei Shen; Qingtao Lv (Journal of Marine Science and Engineering, 2024)
Non-metallic armoured optoelectronic cable winch systems (NAOCWSs) play critical roles in facilitating signal transmission and powering subsea equipment. Due to the varying depths in these applications, deploying the entire cable length is unnecessary. However, the portion of the cable that remains coiled around the winch can generate an electromagnetic field, which may interfere with signal transmission and induce electromagnetic heating. This can lead to elevated temperatures within the system, affecting the cable’s lifespan. Consequently, this study examines the distributions of magnetic and temperature fields within the NAOCWS with different currents (10–30 A) and numbers of winding layers (1–10). Findings indicate that the magnetic flux density (MFD) changes periodically, and the period is closely related to the distance between the cables. At the centre of the cable, the flux density is minimum. Temperature distribution correlates with both current amplitude and the number of winding layers, where an increase in either parameter amplifies the temperature variance between the edge and intermediate cables within the same layer. The current does not affect the internal temperature distribution pattern. With the number of winding layers determined, the layer where the highest temperature of the system is located is well defined and does not vary with current.

Transition from a hydrologically partitioned to an integrated lake in the Cretaceous Junggar Basin, Central Asia - Xutong Guan; Chaodong Wu; Joel Saylor; Weiwei Jia; Xueying Tang; Yizhe Wang; Cong Lin (Journal of Asian Earth Sciences, 2024)

Drivers distinguishing of PAHs heterogeneity in surface soil of China using deep learning coupled with geo-statistical approach - Weiwei Wang; Songchao Chen; Lu Chen; Lingwen Wang; Yang Chao; Zhou Shi; Daohui Lin; Kun Yang (Journal of Hazardous Materials, 2024)

A novel functionalized graphdiyne oxide membrane for efficient removal and rapid detection of mercury in water - Qianli He; Xue Li; Weiwei Chai; Lin Chen; Xuefei Mao (Journal of Hazardous Materials, 2024)

In-situ GSH-responsive gas nanogenerator for active NIR-II FL/PA imaging and synergistic restoration the macrophage niche in rheumatoid arthritis - Xiaochun Zheng; Weiwei Kang; Yarong Jin; Xin Zhang; Wenxuan Wang; Dongsheng Li; Shutong Wu; Lin Chen; Shichao Meng; Rong Dai; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2024)

Three-Dimensional Turbulent Simulation of Bivariate Normal Distribution Protection Device - Jing Liu; Zongyu Li; Hanming Huang; Weiwei Lin; Zhilin Sun; Fanjun Chen (Journal of Marine Science and Engineering, 2024)
In response to the deficiencies in existing bridge pier scour protection technologies, this paper introduces a novel protective device, namely a normal distribution-shaped surface (BND) protection devices formed by rotating a concave normal curve. A three-dimensional turbulent SST k−ω model is constructed, and physical model experiments of conical surfaces are conducted to validate the mathematical model. The simulation analyzes longitudinal water flow, downflow, vorticity intensity, and shear stress within normal and conical surfaces. The results show that the downflow distribution in front of the pier spans a relative water depth of (−0.45, 0.67), with a peak velocity approximately 70% of the longitudinal flow velocity. Circulation forms within the surfaces, with the main vortex flux inside the BND being 33% lower than that inside the conical surface. The maximum shear stress coefficient inside the BND can reach 9, and the protective surface isolates the bed from the flow to prevent scouring by high shear stress. The velocity gradient at the edge of the surface is small, and the edge shear stress of the 3D normal distribution-shaped surface (BND) protection device is only one-third of that of the conical surface, preventing edge scouring. The large shear stress and its distribution area decrease monotonically with the increase in surface width. When the surface width is four times the diameter, the distribution range of the shear stress coefficient greater than 1 is very small. The study of three-Dimensional turbulence within the BND provides a numerical basis for an anti-scour design.

Main effects and interactions of multiple key factors related to thermal perception - Yuxin Yang; Junmeng Lyu; Heng Du; Zhiwei Lian; Weiwei Liu; Lin Duanmu; Yongchao Zhai; Bin Cao; Yufeng Zhang; Xiang Zhou; Zhaojun Wang; Xiaojing Zhang; et al. (Science of The Total Environment, 2024)

Low phosphorus increases hepatic lipid deposition, oxidative stress and inflammatory response via Acetyl-CoA carboxylase-dependent manner in zebrafish liver cells - Jibin Lin; Jilei Zhang; Weiwei Dai; Xiao Li; Mohamed Mohsen; Xueshan Li; Kangle Lu; Kai Song; Ling Wang; Chunxiao Zhang (Fish & Shellfish Immunology, 2024)

Precipitation and plant functional composition mediate desert canopy nutrient responses to water and nitrogen addition - Weiwei She; Yong Zhou; Wentao Luo; Yuxuan Bai; Wei Feng; Zongrui Lai; Yangui Qiao; Liang Liu; Wenjin Zhang; Lin Miao; Chun Miao; Shugao Qin; et al. (Plant and Soil, 2024)

Slow-release fertilizer deep placement increased rice yield and reduced the ecological and environmental impact in Southeast China: A life-cycle perspective - Chaojie Lan; Jingnan Zou; Jinying Li; Hailong Xu; Weiwei Lin; Peiying Weng; Changxun Fang; Zhixing Zhang; Hongfei Chen; Wenxiong Lin (Field Crops Research, 2024)

Rapid visual nucleic acid detection of Vibrio alginolyticus by recombinase polymerase amplification combined with CRISPR/Cas13a - Yanan Wang; Yachao Hou; Xinping Liu; Na Lin; Youyou Dong; Fei Liu; Wenrong Xia; Yongqi Zhao; Weiwei Xing; Jin Chen; Changguo Chen (World Journal of Microbiology and Biotechnology, 2024)

The joint associations of ambient air pollutants and weather factors with mortality: Evidence from a national time-stratified case-crossover study in China - Qijiong Zhu; Min Yu; Guoxia Bai; Chunliang Zhou; Ruilin Meng; Biao Huang; Weiwei Gong; Haoming Zhang; Ruying Hu; Zhulin Hou; Yize Xiao; Donghui Jin; et al. (Science of The Total Environment, 2024)

Aerobic methane production by phytoplankton as an important methane source of aquatic ecosystems: Reconsidering the global methane budget - Yufeng Mao; Tong Lin; Hong Li; Ruixu He; Kailai Ye; Weiwei Yu; Qiang He (Science of The Total Environment, 2024)

Performance and uncertainties of five popular satellite-based precipitation products in drought monitoring for different climate regions - Yanzhong Li; Haiwen Yan; Li Chen; Manjie Huang; Weiwei Shou; Liqin Zhu; Lin Zhao; Yincong Xing (Journal of Hydrology, 2024)

Exploring the therapeutic potential of layered double hydroxides and transition metal dichalcogenides through the convergence of rheumatology and nanotechnology using generative adversarial network - Suxian Lin; Weiwei Chen; Mohammed S. Alqahtani; Dalia H. Elkamchouchi; Yisu Ge; Yanjie Lu; Guodao Zhang; Mudan Wang (Environmental Research, 2024)

Electronic regulation of MoS2 edge sites by d electron transfer of Ni or Co to improve the activity of CO sulfur-resistant methanation - Qiang Wang; Weiwei Huang; Xin Li; Shuangxi Lin; Zhenhua Li; Xinbin Ma (Chemical Engineering Journal, 2024)

Fluorine modification regulation of D-A ambipolar conducting polymers towards high-performance energy storage device - Weiwei Hou; Shenglian Yao; Yusheng Chen; Dianyu Tang; Yijing Gao; Xiangyu Zhang; Ling Zhang; Zhenliang Zhang; Mi Ouyang; Junlei Liu; Lin Gu; Cheng Zhang (Chemical Engineering Journal, 2024)

Anthropogenic activities altering the ecosystem in Lake Yamzhog Yumco, southern Qinghai-Tibetan Plateau - Wu Han; Enlou Zhang; Weiwei Sun; Qi Lin; Xianqiang Meng; Zhenyu Ni; Dongliang Ning; Ji Shen (Science of The Total Environment, 2023)

Ecological benefits of artificial light at night (ALAN): Accelerating the development and metamorphosis of marine shellfish larvae - Mo Zhang; Xiaolong Gao; Qi Luo; Shihui Lin; Mingxin Lyu; Xuan Luo; Caihuan Ke; Weiwei You (Science of The Total Environment, 2023)

The association of heatwave with drowning mortality in five provinces of China - Zhongguo Huang; Zhixing Li; Jianxiong Hu; Sui Zhu; Weiwei Gong; Chunliang Zhou; Ruilin Meng; Xiaomei Dong; Min Yu; Xiaojun Xu; Lifeng Lin; Jianpeng Xiao; et al. (Science of The Total Environment, 2023)

Bridge frequency identification in city bus monitoring: A coherence-PPI algorithm - Yifu Lan; Zhenkun Li; Keijo Koski; Ludovic Fülöp; Timo Tirkkonen; Weiwei Lin (Engineering Structures, 2023)

Integrating ferroptosis-related genes (FRGs) and prognostic models to enhance UCEC outcome prediction and therapeutic insights - Weiwei Jin; Xiaoping Zhuang; Yihe Lin; Xiaoying Zhao (Journal of Applied Genetics, 2023)

Leaf thermal regulation strategies of canopy species across four vegetation types along a temperature and precipitation gradient - Yingying Zhou; Nawatbhrist Kitudom; Sophie Fauset; Martijn Slot; Zexin Fan; Jianping Wang; Weiwei Liu; Hua Lin (Agricultural and Forest Meteorology, 2023)

Genetic Diversity and Genetic Structure among Four Selected Strains of Whiteleg Shrimp (Litopenaeus vannamei) Using SSR Markers - Zhe Zhang; Chengkuan Lu; Kebing Lin; Weiwei You; Zhangwu Yang (Fishes, 2023)
The whiteleg shrimp (Litopenaeus vannamei) is one of the most economically important aquaculture species in China. Genetic diversity is crucial for maintaining the gene pool of farmed shrimp. In this study, the effects of artificial selection on the genetic structure of four whiteleg shrimp strains were evaluated using microsatellite sequences. The results showed that the observed heterozygosity (Ho), expected heterozygosity (He), and the polymorphism information content (PIC) of the four selected strains ranged from 0.446 to 0.574, 0.450 to 0.566, and 0.435 to 0.509, respectively. All the selected strains maintained a moderate level of genetic diversity. Most inbreeding coefficients (Fis) in the four strains were positive but not significantly different from zero, indicating a relatively low degree of inbreeding within each strain. However, He and PIC in line 5 showed a decreasing trend from the 2017 to the 2019 generations, and Fis in line 10 showed a significant increasing trend across generations, indicating that measures must be taken to maintain the level of genetic diversity for lines 5 and 10. UPGMA cluster trees showed that the four breeding lines had apparent genetic differences, which could provide a genetic basis for studying crossbreeding between selective lines and the utilization of heterosis. This study will be useful for population genetic research and the breeding strategies of whiteleg shrimp.

Role of antenatal anxiety in the relationship between maternal exposure to nitrogen dioxide and small for gestational age: A birth cohort study - Qiannan Wei; Weiwei Lin; Hedi Zhang; Yuming Lai; Shuling Zhuang; Zhenyan Han; Qingqing Wang; Lijie Wang; Wenzhuo Li; Li Wen; Hongying Hou; Qiansheng Hu (Science of The Total Environment, 2023)

Design of rich defects carbon coated MnFe2O4/LaMnO3/LaFeO3 heterostructure nanocomposites for broadband electromagnetic wave absorption - Xinyang Liu; Lin He; Guanghui Han; Jie Sheng; Yongsheng Yu; Weiwei Yang (Chemical Engineering Journal, 2023)

Ester tethered artemisinin-isatin hybrids: design, synthesis and anti-leukemic activity evaluation - Peng Wang; Dai Yuan; Weiwei Wang; Lei Zhou; Lin Wang; Yang Zhao; Jiarui Xu; Li Kong (Medicinal Chemistry Research, 2023)

Examination of the effects of blue light stress on monoamine oxidase-mediated immunomodulatory function in the Pacific abalone, Haliotis discus hannai - Mo Zhang; Xiaolong Gao; Mingxin Lyu; Shihui Lin; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2023)

The effects of prenatal PM2.5 oxidative potential exposure on feto-placental vascular resistance and fetal weight: A repeated-measures study - Weiwei Lin; Yuming Lai; Shuling Zhuang; Qiannan Wei; Hedi Zhang; Qiansheng Hu; Peng Cheng; Manman Zhang; Yuhong Zhai; Qingqing Wang; Zhenyan Han; Hongying Hou (Environmental Research, 2023)

Plant selection and ecological microhabitat drive the shrub-associated microbiome selection in revegetated shrub ecosystems - Zongrui Lai; Yanfei Sun; Yang Yu; Zhen Liu; Yuxuan Bai; Yangui Qiao; Lin Miao; Weiwei She; Shugao Qin; Wei Feng (Applied Soil Ecology, 2023)

Forearc spreading cessation and backarc basin evolution: Insights from Mariana subduction system and geodynamic modeling - Zihua Cheng; Fan Zhang; Jian Lin; Weiwei Ding; Xubo Zhang (Tectonophysics, 2023)

Indirect damage detection for bridges using sensing and temporarily parked vehicles - Zhenkun Li; Yifu Lan; Weiwei Lin (Engineering Structures, 2023)

Detachment-controlled subsidence pattern at hyper-extended passive margin: Insights from backstripping modelling of the Baiyun Rift, northern South China Sea - Penggao Fang; Weiwei Ding; Yanghui Zhao; Xiubin Lin; Zhongxian Zhao (Gondwana Research, 2023)

In situ construction of MnIn2S4/Ti3C2TxMXene Schottky junction composites for efficient photoreduction and recovery of U(VI) - Yingjun Wang; Longyu Qiu; Shuangyou Bao; Fenyang Tian; Lin He; Weiwei Yang; Yequn Liu; Yongsheng Yu (Chemical Engineering Journal, 2023)

Detoxification and removal of arsenite by Pseudomonas sp. SMS11: Oxidation, biosorption and bioaccumulation - Xiaoman He; Weiwei Xiao; Jiayuan Zeng; Jie Tang; Lin Wang (Journal of Environmental Management, 2023)

Genome-wide Association Study of Root Hair Length in Maize - Li Xuhui; Lu Siqi; Chen Weiwei; Zhu Hang; Lin Huanzhang; Fu Danwen; Fan Lina; Fang Junteng; Hu Yuanqiang; Zhang Xiangbo; Chang Hailong; Qi Yongwen (Tropical Plant Biology, 2023)

Consistent differences in brain structure and functional connectivity in high-altitude native Tibetans and immigrants - Xinjuan Zhang; Weiwei Xie; Wenrui Du; Yanqiu Liu; Jianzhong Lin; Wu Yin; Lihui Yang; Fengjuan Yuan; Ran Zhang; Haipeng Liu; Hailin Ma; Jiaxing Zhang (Brain Imaging and Behavior, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Investigation on the formation mechanism of main products from TBBPA pyrolysis using DFT method - Xin Mu; Yao Wang; Jinbao Huang; Lin Lan; Hong Wang; Weiwei Xu; Xinsheng Li (Chemosphere, 2023)

On-road mobile mapping of spatial variations and source contributions of ammonia in Beijing, China - Weiwei Pu; Jiujiang Sheng; Ping Tian; Mengyu Huang; Xiangxue Liu; Jeffrey L. Collett; Ziming Li; Xiujuan Zhao; Di He; Fan Dong; Nannan Zhang; Weijun Quan; et al. (Science of The Total Environment, 2023)

Simultaneous dual-defect engineering as a booster for polysulfide adsorption and conversion in Li-S battery - Meixiu Qu; Yu Bai; Weiwei Yang; Lin Peng; Zhenhua Wang; Wang Sun; Kening Sun (Chemical Engineering Journal, 2023)

Efficient electromagnetic wave absorption and Joule heating via ultra-light carbon composite aerogels derived from bimetal-organic frameworks - Weiwei He; Jiajia Zheng; Weiping Dong; Shaohua Jiang; Gang Lou; Lin Zhang; Wenya Du; Zhaochun Li; Xiping Li; Yiming Chen (Chemical Engineering Journal, 2023)

Coupling of leaf elemental traits with root fungal community composition reveals a plant resource acquisition strategy in a desert ecosystem - Yangui Qiao; Liang Liu; Chun Miao; Guannan Zhu; Lin Miao; Weiwei She; Shugao Qin; Yuqing Zhang (Plant and Soil, 2023)

The second-generation real-time ecological environment prediction system for the Guangdong–Hong Kong–Marco Greater Bay Area: Model setup, validation, improvements, and online visualization - Lin Luo; Zhao Meng; Weiwei Ma; Jingwen Huang; Youchang Zheng; Yang Feng; Yineng Li; Yonglin Liu; Yuanguang Huang; Yuhang Zhu (Frontiers in Marine Science, 2023)
With the rapidly growing population and socioeconomic development of the Guangdong–Hong Kong–Marco Greater Bay Area of China, inputs of diverse contaminants have rapidly increased. This poses threats to the water quality of the Pearl River Estuary (PRE) and adjacent seas. To provide valuable information to assist the governors, stakeholders, and decision-makers in tracking changes in environmental conditions, daily nowcasts and two-day forecasts from the ecological prediction system, namely the Coupled Great Bay Ecological Environmental Prediction System (CGEEPS), has been setup. These forecast systems have been built on the Coupled Ocean–Atmosphere–Wave–Sediment Transport modelling system. This comprises an atmospheric Weather Research Forecasting module and an oceanic Regional Ocean Modelling System module. Daily real-time nowcasts and 2-day forecasts of temperature, salinity, NO2 + NO3, chlorophyll, and pH are continuously available. Visualizations of the forecasts are available on a local website ( http://www.gbaycarbontest.xyz:8008/ ). This paper describes the setup of the environmental forecasting system, evaluates model hindcast simulations from 2014 to 2018, and investigates downscaling and two-way coupling with the regional atmospheric model. The results shown that though CGEEPS lacks accuracy in predicting the absolute value for biological and biogeochemical environmental variables. It is quite informative to predict the spatio-temporal variability of ecological environmental changes associated with extreme weather events. Our study will benefit of developing real-time marine biogeochemical and ecosystem forecast tool for oceanic regions heavily impact by extreme weathers.

Development of a low-density SNP genotyping panel by a novel technology mGPS and its application in germplasm identification of abalone - Weihong Lin; Qizhen Xiao; Feng Yu; Zhaofang Han; Junyu Liu; Wenzhu Peng; Zekun Huang; Yuting Lei; Weiguo Li; Weiwei You; Xuan Luo; Caihuan Ke (Aquaculture, 2023)

Spatiotemporal patterns of organic carbon burial over the last century in Lake Qinghai, the largest lake on the Tibetan Plateau - Xianqiang Meng; Xi Chen; Qi Lin; Yilan Liu; Zhenyu Ni; Weiwei Sun; Enlou Zhang (Science of The Total Environment, 2023)

Utility of outdoor central site monitoring in assessing exposure of school children to ultrafine particles - Basant Pradhan; Rohan Jayaratne; Helen Thompson; Giorgio Buonanno; Mandana Mazaheri; Mawutorli Nyarku; Weiwei Lin; Marcelo Luiz Pereira; Josef Cyrys; Annette Peters; Lidia Morawska (Science of The Total Environment, 2023)

Engineering electron redistribution of bimetallic phosphates with CeO2 enables high-performance overall water splitting - Xin Guo; Menggang Li; Longyu Qiu; Fenyang Tian; Lin He; Shuo Geng; Yequn Liu; Ying Song; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2023)

Theoretical study on pyrolysis mechanism of decabromodiphenyl ether (BDE-209) using DFT method - Yao Wang; Jinbao Huang; Hong Wang; Lin Lan; Xin Mu; Weiwei Xu; Shanjin Lv; Xinsheng Li (Chemosphere, 2023)

Diagnosis algorithms for indirect bridge health monitoring via an optimized AdaBoost-linear SVM - Yifu Lan; Youqi Zhang; Weiwei Lin (Engineering Structures, 2023)

Structural modification enhances the electrochemical performance for organic cathode materials - Shuai Liu; Fei Peng; Yilin Lin; Wenjun Zhou; Weiwei Huang (Chemical Engineering Journal, 2023)

Meniscus inspired flexible superhydrophobic coating with remarkable erosion resistance for pipeline gas transmission - Xuerui Zang; Xuewen Cao; Weiwei Zheng; Tianxue Zhu; Yonggang Lei; Jianying Huang; Zhong Chen; Lin Teng; Jiang Bian; Yuekun Lai (Chemical Engineering Journal, 2023)

Mechanically strong and biodegradable holocellulose films prepared from Camellia oleifera shells - Haibo Long; Jin Gu; Jianchun Jiang; Litao Guan; Xiuyi Lin; Weiwei Zhang; Chuanshuang Hu (Carbohydrate Polymers, 2023)

TRIM46 upregulates Wnt/β-catenin signaling by inhibiting Axin1 to mediate hypoxia-induced epithelial–mesenchymal transition in HK2 cells - Lin Liao; Lianxiang Duan; Yue Guo; Baojuan Zhou; Qiming Xu; Chuanfu Zhang; Weiwei Liu; Wenrui Liu; Ziyang Liu; Jing Hu; Jie Chen; Jianrao Lu (Molecular and Cellular Biochemistry, 2022)

Study on the Contribution of Seaport to Urban Economy: An Empirical and Quantitative Analysis of Xiamen Port - Wei Liu; Yanbin Yang; Qiaoyun Luo; Xufeng Zeng; Chuxin Chen; Junfeng Zhu; Weishan Lin; Hongbin Chen; Weiwei Huo; Mengxiao He; Yuping Jin; Jiangyu Xu (Journal of Marine Science and Engineering, 2022)
Ports play a vital role in the development of cities. In order to study the contribution of seaports to the urban economy, this paper uses the input–output method and multiplier theory to calculate the direct, indirect, and ripple economic contribution of ports to cities. Then, this paper selects Xiamen Port as an example to calculate the economic contribution. Xiamen Port is a major port on the southeast coast of China and an important node of the 21st Century Maritime Silk Road. It can provide a reference for other port cities. A more detailed index system for evaluating the economic contribution is also constructed. Next, the time series ARIMA model is used to predict the cargo throughput and container throughput of Xiamen Port in the next four years. Finally, there are some suggestions put forward for the development of Xiamen Port. The results show the total economic contribution of Xiamen Port to the city accounted for 10.48% of the city’s GDP in 2017. Direct, indirect, and ripple economic contributions accounted for 2.84%, 2.13%, and 5.51%, respectively. The contribution of Xiamen Port to the city is in line with the growth pole theory, which not only allows for rapid growth in Xiamen Port itself but also drives the development of the entire region through the multiplier effect. The cargo throughput and container throughput of Xiamen Port will maintain continuous growth in the next four years. Therefore, the development of Xiamen Port should be accelerated to enhance its economic contribution to the city.

Novel Self-Assembled Micelles With Increased Tumor Penetration and Anti-Tumor Efficiency Against Breast Cancer - Yani Yang; Yuezhu Zhao; Jie Liu; Chen Ge; Weiwei Zhang; Yue Zhang; Junji Wang; Guohao Sun; Xiujun Lin; Xiaohong Lu; Xiang Tang; Jun He; et al. (Pharmaceutical Research, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Identification, Phylogeny and Expressional Profiles of Peptidoglycan Recognition Protein (PGRP) Gene Family in Sinonovacula constricta - Yiping Meng; Liyuan Lü; Wenfang Dai; Weiwei Zhang; Zhihua Lin; Yinghui Dong (Journal of Ocean University of China, 2022)

Erratum to: Chinia gen. nov.—the second diatom genus simonsenioid raphe from mangroves in Fujian, China - Huina Lin; Weiwei Wu; Lin Sun; Andrzej Witkowski; Xiaoye Li; Vishal Patil; Junrong Liang; Xuesong Li; Yahui Gao; Changping Chen (Journal of Oceanology and Limnology, 2022)

Chinia gen. nov.—the second diatom genus simonsenioid raphe from mangroves in Fujian, China - Huina Lin; Weiwei Wu; Lin Sun; Andrzej Witkowski; Xiaoye Li; Vishal Patil; Junrong Liang; Xuesong Li; Yahui Gao; Changping Chen (Journal of Oceanology and Limnology, 2022)

Evolutionary and ecological patterns of scatter‐ and larder‐hoarding behaviours in rodents - Yongjun Zhang; Fei Yu; Xianfeng Yi; Weiwei Zhou; Rui Liu; Marcel Holyoak; Lin Cao; Mingming Zhang; Jiani Chen; Zhibin Zhang; Chuan Yan (Ecology Letters, 2022)
Scatter‐ and larder hoarding are the primary strategies of food‐hoarding animals and have important implications for plant‐animal interactions and plant recruitment. However, their origins and influencing factors have not been fully investigated across a wide range of taxa. Our systematic literature search amassed data for 183 seed‐hoarding rodent species worldwide and tested relationships of seed‐hoarding behaviours with phylogenetic signal, functional traits and environmental factors. We found that the evolution of hoarding strategies was not random in phylogeny, and scatter hoarding originated independently multiple times from larder hoarding. Rodents with higher encephalisation quotient (relative brain size), omnivorous diet (related to dependence on seeds) and inhabiting lower latitudes were disproportionately likely to scatter hoard. Despite body mass’s potential relationship with competition through food defence, it was associated with food‐hoarding strategy only in a few families. Our results show the need to study the community and ecological context of food‐hoarding behaviours.

Preparation of carbonyl, hydroxyl, and amino-functionalized microporous carbonaceous nanospheres from syrup-based waste to remove sulfamethazine - Xiaohong Hu; Yang Huang; Zhong Pan; Shunxing Li; Qiao Li; Weiwei Lin (Environmental Science and Pollution Research, 2022)

IgE Reactivity of Potential Allergens from the Swimming Crab Portunus trituberculatus and the Research of ELISA Reagent for Detecting Crab Food Anaphylaxis - Xueni Qiu; Qiongyan Zhou; Xiaoxia Zhu; Wei Lin; Changkao Mu; Ronghua Li; Yangfang Ye; Weiwei Song; Ce Shi; Lei Liu; Huan Wang; Chunlin Wang; et al. (Journal of Ocean University of China, 2022)

Taxonomy and Phylogeny of Two Tintinnid Ciliates of Leprotintinnus (Protista, Ciliophora, Choreotrichida) Combining the Loricae, Cytological, Ontogenetic Features, and Barcoding Genes - Tao Hu; Zhaoyi Wang; Weiwei Liu; Xiaofeng Lin (Frontiers in Marine Science, 2022)
Tintinnid ciliates are a highly diverse and essential group in the marine planktonic microbial loop. However, most of the known tintinnids were recorded only by the lorica characters and very few of them had been studied on their cytological features. In this study, the morphological characters of the lorica, ciliary pattern, nuclear apparatus, ontogenesis, and the molecular phylogeny of two poorly known tintinnid ciliates, Leprotintinnus nordqvisti ( Brandt, 1906 ) Kofoid and Campbell (1929) and L. simplex Schmidt (1902) , isolated from coastal waters of southern China, were investigated based on living observation, silver staining, three nuclear ribosomal DNA markers (18S, ITS1-5.8S-ITS2, and 28S genes) and one mitochondrial DNA marker ( CO1 gene). For the first time, the somatic ciliary pattern of the genus Leprotintinnus was disclosed, viz ., comprising a ventral, a dorsal, and a posterior kinety as well as a right, a left, and a lateral ciliary field. The diagnoses of both Leprotintinnus species were improved and the neotype was assigned. The ontogenesis of L. nordqvisti was in enantiotropic division mode with the new dorsal and posterior kineties generated de novo . The molecular phylogeny confirmed that Leprotintinnus species are closely related to some species of Tintinnopsis , Stylicauda , Rhizodomus , and Climacocylis . The anterior extending of the ventral kinety together with some of the lateral kinety is likely to be a distinguishing feature to determine their systematic relationships. This study also revealed that (i) the lorica of L. nordqvisti is polymorphic or plastic; (ii) Leprotintinnus tubulosus Roxas (1941) might be a synonym of L . nordqvisti ; (iii) Leprotintinnus neriticus sensu Yoo et al. (1988) might be a misidentification of L. simplex .

Bioaccessibility of Cd and its Correlation with Divalent Mineral Nutrients in Locally Grown Rice from Two Provinces in China - Peng Liu; Weiwei Xiao; Kai Wang; Zhaoguang Yang; Lin Wang (Biological Trace Element Research, 2022)

Description and genome analysis of Microvirga antarctica sp. nov., a novel pink-pigmented psychrotolerant bacterium isolated from Antarctic soil - Lin Zhu; Weiwei Ping; Siyue Zhang; Ya Chen; Ying Zhang; Jianli Zhang (Antonie van Leeuwenhoek, 2021)

Effects of Flow Velocity on the Growth and Survival of Haliotis discus hannai Larvae in the Recirculating Upflow System From the Point of Energy Metabolism - Mo Zhang; Xiaolong Gao; Mingxin Lyu; Shihui Lin; Ying Su; Xuan Luo; Weiwei You; Caihuan Ke (Frontiers in Marine Science, 2021)
For the abalone Haliotis discus hannai , attachment and metamorphosis are crucial stages in the transition from planktonic to benthic life. Increasing the larval metamorphosis rate by artificially controlling the external environment and simulating natural seawater flow is vital to enhance the hatchery efficiency of H. discus hannai . Thus, in the current study, an upflow recirculating aquaculture unit was designed for the rearing of larval abalone, and the larval hatching rate, survival rate, mode of energy metabolism, and expression levels of metamorphosis-related genes at different flow velocities (0, 5, 10, 20, and 40 L/h) were compared and analyzed. At flow velocities less than 20 L/h, no significant differences occurred in larval hatching, survival, and metamorphosis rates, whereas significant differences were recorded at flow rates of 20 and 40 L/h. Differences were also observed in the activity of enzymes, such as hexokinase (HK), pyruvate kinase (PK), lactate dehydrogenase (LDH), succinate dehydrogenase (SDH), and malate dehydrogenase (MDH), as well as glycogen levels, at the higher flow rates. These results suggested that velocity in excess of a certain limit leads to a higher glycolysis rate and transition of energy utilization from aerobic to anaerobic metabolism for the abalone larvae. Compared with conventional still-water aquacultural systems, the flow velocity at 5–10 L/h could maintain the water environment stability, and avoid both fertilized eggs from being densely deposited before hatching and the consumption of energy needed to resist high flow velocities. Thus, these results are useful references to enhance the hatchery efficiency, and to conduct large-scale rearing, of abalone larvae.

The impact of green credit policy on energy efficient utilization in China - Xiaowei Ma; Weiwei Ma; Lin Zhang; Yi Shi; Yuping Shang; Huangxin Chen (Environmental Science and Pollution Research, 2021)

Comparative Study of the Feeding Characteristics and Digestion Physiology of Haliotis discus hannai and Haliotis gigantea - Mingxin Lyu; Xiaolong Gao; Mo Zhang; Shihui Lin; Xuan Luo; Weiwei You; Caihuan Ke (Frontiers in Marine Science, 2021)
Abalone ( Haliotis spp.) are typical nocturnal creatures but Haliotis discus hannai is bold and active in the nighttime whereas H. gigantea tends to be timid and inactive. In this study, we quantified and compared differences in movement, feeding, and digestive physiology between H. discus hannai and H. gigantea as well as the potential molecular mechanisms on the basis of video observations and expression levels of genes related to feeding regulation. The feeding behaviors of both species were characterized by significant circadian rhythms ( P < 0.05). However, the distance moved and the cumulative duration of movement were 2.61 and 1.94 times higher, respectively, in H. discus hannai than in H. gigantea over the 24-h cycle. The cumulative duration of feeding by H. discus hannai was only 1.15 times that by H. gigantea , but the feeding time as a percentage of the cumulative duration of movement (FTP) was up to 94.6% for H. gigantea and only 56.0% for H. discus hannai . The peaks for α-amylase activity and NPF expression levels in both species as well as the peak OX 2 R expression level in H. gigantea occurred during 20:00–00:00 h. By contrast, the peaks for alginate lyase activity and NPYR expression levels in H. discus hannai occurred at 16:00 h, when the FTP was significantly higher for H. discus hannai than for H. gigantea . These initial findings quantify specific behavior parameters and thus provide a reference for the selection of appropriate feeding strategies and the proliferation of abalone via bottom sowing.

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Insights from comparative proteomic analysis into degradation of phenanthrene and salt tolerance by the halophilic Martelella strain AD-3 - Xin Chen; Weiwei Wang; Haiyang Hu; Hongzhi Tang; Yongdi Liu; Ping Xu; Kuangfei Lin; Changzheng Cui (Ecotoxicology, 2021)

Genetic Diversity in Marine Planktonic Ciliates (Alveolata, Ciliophora) Suggests Distinct Geographical Patterns – Data From Chinese and European Coastal Waters - Maximilian H. Ganser; Dominik Forster; Weiwei Liu; Xiaofeng Lin; Thorsten Stoeck; Sabine Agatha (Frontiers in Marine Science, 2021)
Unraveling geographic distribution patterns of planktonic protists is a central goal in marine microbial ecology. Using a novel combination of recently developed phylogenetic and network analyses on a V4 18S rDNA metabarcoding dataset, we here analyzed the genetic diversity of marine planktonic ciliate communities in Chinese and European coastal waters. Thereby, our approach provided an unprecedented perspective on geographic patterns inferred from ciliate genetic diversity and accomplished a very fine resolution down to single nucleotides within operational taxonomic units (OTUs). While most OTUs (87%) exclusively contained sequences of either Chinese or European origin, those OTUs detected in both regions comprised the vast majority of reads (84%). Phylogenetic analyses of OTUs belonging to the same taxon revealed genetically distinct clades that were geographically restricted to either Chinese or European coastal waters. The detection of signature nucleotides emphasized this genetic distinction of Chinese and European clades. Second-level clustering of OTUs and reference sequences in two selected taxa (the oligotrichid Spirotontonia and the tintinnid Tintinnidium ) revealed the presence of several potentially new species or ones lacking genetic reference data. Geographic patterns were also discovered by network analyses within 700 widespread and abundant OTUs; in 77 of these OTUs, European and Chinese sequences formed significantly assortative groups. These assortative groupings indicated a higher genetic similarity among sequences from the same region than between sequences from different regions. Our results demonstrate that detailed analyses of metabarcoding data down to single nucleotide differences expand our perception of geographical distribution patterns and provide insights into historic and ongoing effective dispersal in protists. The congruent discovery of geographic patterns at different levels of resolution (between and within OTUs) suggests that cosmopolitan distribution in marine planktonic ciliates is less common than previously postulated.

Novel Contributions to the Taxonomy of the Ciliates Genus Euplotes (Ciliophora, Euplotida): Redescription of Two Poorly Known Species, With a Brief Note on the Distributions of This Genus in Coastal Waters of Southern China - Weiwei Liu; Jiamei Jiang; Yehui Tan; Xiaofeng Lin (Frontiers in Marine Science, 2020)
As the typical periphytic ciliate, the genus Euplotes Ehrenberg, 1830 is highly diversified and commonly observed in marine water. In this study, the living morphology, infraciliature and silverline system of two poorly known Euplotes species, E. neapolitanus Wichterman, 1964 and E. antarcticus Fenchel and Lee, 1972 , isolated from coastal water of southern China, were investigated. The original description of these two species were brief, and thus we provided detailed redescription based on our Chinese population. Their diagnoses were improved by adding some morphology characteristics and their detailed illustrations and photomicrographs were first supplied here. Based on the sufficient justification for identification of our population by morphology, their small subunit ribosomal RNA gene sequences which have been reported were linked to the accurate species name. Phylogenetic analyses showed that these two species cluster with their congeners which shared high morphological similarities with them. In addition, the geographic distribution of the genus Euplotes in coast of southern China was revealed, and the mangrove was considered as the ideal habitat for them by possessing the higher species richness.

An allotriploid hybrid developed from a female 2n gamete was obtained from Eriobotrya japonica (Thunb.) Lindl × E. deflexa (Hemsl.) Nakai - Yanjuan Song; Jiangbo Dang; Weiwei Chen; Guo Wen; Qiao He; Xiaolin Li; Shoukai Lin; Guolu Liang; Qigao Guo (Euphytica, 2020)

Genomewide analysis of microsatellite markers based on sequenced database in two anuran species - LI WEI; WEIWEI SHAO; LI MA; ZHIHUA LIN (Journal of Genetics, 2020)

Chemoheterotrophic diazotrophs contribute to nitrogen incorporation in a semi-arid desert - Lin Miao; Wei Feng; Yuqing Zhang; Yuxuan Bai; Yanfei Sun; Weiwei She; Henan Mao; Zongrui Lai; Shugao Qin (Biology and Fertility of Soils, 2020)

Erratum to: An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Simulation of oyster ecological carrying capacity in Sanggou Bay in the ecosystem context - Yaping Gao; Jianguang Fang; Fan Lin; Fengxue Li; Wenhao Li; Xiaoqin Wang; Meirong Du; Jinghui Fang; Weiwei Jiang; Hui Liu; Yitao Zhang; Junwei Wang; et al. (Aquaculture International, 2020)

An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Taxonomy and Phylogeny of a New Marine Planktonic Ciliate, Strombidium pseudorapulum sp. n. (Protozoa, Ciliophora, Oligotrichia) - Fenfen Li; Yaoyao Huang; Ying Yu; Weiwei Liu; Xiaofeng Lin (Journal of Ocean University of China, 2020)

Taurine attenuates isoproterenol-induced H9c2 cardiomyocytes hypertrophy by improving antioxidative ability and inhibiting calpain-1-mediated apoptosis - Weiwei Li; Jiancheng Yang; Qiufeng Lyu; Gaofeng Wu; Shumei Lin; Qunhui Yang; Jianmin Hu (Molecular and Cellular Biochemistry, 2020)

Asymmetry in oceanic crustal structure of the South China Sea basin and its implications on mantle geodynamics - Fan Zhang; Jian Lin; Xubo Zhang; Weiwei Ding; Tingting Wang; Jian Zhu (International Geology Review, 2020)

Liver X receptor activation induces podocyte injury via inhibiting autophagic activity - Ziyi Zhang; Shengjie Tang; Weiwei Gui; Xihua Lin; Fenping Zheng; Fang Wu; Hong Li (Journal of Physiology and Biochemistry, 2020)

Three-dimensional reconstruction of Picea wilsonii Mast. pollen grains using automated electron microscopy - Weiwei Shen; Lingyu Ma; Xi Zhang; Xixia Li; Yuanyuan Zhao; Yanping Jing; Yun Feng; Xueke Tan; Fei Sun; Jinxing Lin (Science China Life Sciences, 2020)

Enzyme-treated soy protein supplementation in low protein diet improved flesh tenderness, juiciness, flavor, healthiness, and antioxidant capacity in on-growing grass carp (Ctenopharyngodon idella) - Yan Song; LiangChao Yan; WeiDan Jiang; WeiWei Xiao; Lin Feng; Pei Wu; Yang Liu; ShengYao Kuang; Ling Tang; XiaoQiu Zhou (Fish Physiology and Biochemistry, 2020)

Simulation of Yesso scallop, Patinopecten yessoensis, growth with a dynamic energy budget (DEB) model in the mariculture area of Zhangzidao Island - Weiwei Jiang; Fan Lin; Meirong Du; Jianguang Fang; Jinghui Fang; Yaping Gao; Xiaoqin Wang; Fengxue Li; Shipeng Dong; Xing Hou; Zengjie Jiang (Aquaculture International, 2020)

Overview of the biodiversity and geographic distribution of aloricate oligotrich ciliates (Protozoa, Ciliophora, Spirotrichea) in coastal waters of southern China - Weiwei Liu; Kexin Zhang; Changzhi Chen; Jiqiu Li; Yehui Tan; Alan Warren; Xiaofeng Lin; Weibo Song (Systematics and Biodiversity, 2019)

Molecular evolution and lineage-specific expansion of the PP2C family in Zea mays - Kai Fan; Shuna Yuan; Jie Chen; Yunrui Chen; Zhaowei Li; Weiwei Lin; Yongqiang Zhang; Jianping Liu; Wenxiong Lin (Planta, 2019)

Individual variation in advertisement calls of the pale-shouldered horned toad (Xenophrys boettgeri) - Li Wei; Cuntong Zhou; Weiwei Shao; Huanzong Lei; Zhihua Lin (acta ethologica, 2019)

Development and chemical characterization of Casparian strips in the roots of Chinese fir (Cunninghamia lanceolata) - Chengwei Song; Weiwei Shen; Liang Du; Jialong Wen; Jinxing Lin; Ruili Li (Trees, 2019)

Simple method for preserving large quantity of high viability red biomass of Haematococcus in the medium term (3~6 months) - Junfeng Wang; Weiwei Tang; Lin Chen; Wen Liu; Xin Gao; Tianzhong Liu (Journal of Applied Phycology, 2019)

Sex differences in neurocognitive screening among adults living with HIV in China - Xiaotong Qiao; Haijiang Lin; Xiaoxiao Chen; Chenxi Ning; Keran Wang; Weiwei Shen; Xiaohui Xu; Xiaoyi Xu; Xing Liu; Na He; Yingying Ding (Journal of NeuroVirology, 2019)

Response of Yesso scallop Patinopecten yessoensis to acute temperature challenge: physiological and biochemical parameters - Weiwei Jiang; Meirong Du; Jianguang Fang; Yaping Gao; Yuze Mao; Qionglin Chen; Fan Lin; Zengjie Jiang (Journal of Oceanology and Limnology, 2019)

Insight into Bacterial Community Diversity and Monthly Fluctuations of Medicago sativa Rhizosphere Soil in Response to Hydrogen Gas Using Illumina High-Throughput Sequencing - Zhiying Li; Xin Liu; Ruirui Liu; Lulu Li; Lin Wang; Weiwei Wang (Current Microbiology, 2018)

Taraxasterol suppresses the growth of human liver cancer by upregulating Hint1 expression - Tianhao Bao; Yang Ke; Yifan Wang; Weiwei Wang; Yuehua Li; Yan Wang; Xiang Kui; Qixin Zhou; Han Zhou; Cheng Zhang; Dongming Zhou; Lin Wang; et al. (Journal of Molecular Medicine, 2018)

Effects of temperature on the survival, feeding, and growth of pearl gentian grouper (female Epinephelus fuscoguttatus × male Epinephelus lanceolatus) - Zhe Zhang; Zhangwu Yang; Ning Ding; Weiwei Xiong; Guofu Zheng; Qi Lin; Gen Zhang (Fisheries Science, 2018)

Characterization of 25 microsatellite loci for the Guenther’s frog Hylarana guentheri - Weiwei Shao; Zhihua Lin; Xiaoli Fan; Guohua Ding; Li Wei (Conservation Genetics Resources, 2018)

Significance of temperature and water availability for soil phosphorus transformation and microbial community composition as affected by fertilizer sources - Dasheng Sun; Qingfang Bi; Kejie Li; Peibin Dai; Yan Yu; Weiwei Zhou; Ting Lv; Xipeng Liu; Jun Zhu; Qichun Zhang; Chongwei Jin; Lingli Lu; et al. (Biology and Fertility of Soils, 2018)

Interaction Effects between HIV and Aging on Selective Neurocognitive Impairment - Yingying Ding; Haijiang Lin; Weiwei Shen; Qionghai Wu; Meiyang Gao; Na He (Journal of Neuroimmune Pharmacology, 2017)

Supplementation of enzyme-treated soy protein saves dietary protein and promotes digestive and absorptive ability referring to TOR signaling in juvenile fish - Weiwei Xiao; Weidan Jiang; Lin Feng; Yang Liu; Pei Wu; Jun Jiang; Yongan Zhang; Xiaoqiu Zhou (Fish Physiology and Biochemistry, 2017)

Identification of CHCHD10 Mutation in Chinese Patients with Alzheimer Disease - Tingting Xiao; Bin Jiao; Weiwei Zhang; Chuzheng Pan; Jingya Wei; Xiaoyan Liu; Yafang Zhou; Lin Zhou; Beisha Tang; Lu Shen (Molecular Neurobiology, 2017)

Carbon reserve and remobilization in leaf sheaths during the grain-filling stage in response to leaf early senescence - Zhaowei Li; Fubiao Wang; Weiwei Lin; Qian Zhao; Jianchao Liu; Fangmin Cheng (Acta Physiologiae Plantarum, 2017)

MeHg Suppressed Neuronal Potency of Hippocampal NSCs Contributing to the Puberal Spatial Memory Deficits - Jianying Tian; Yougen Luo; Weiwei Chen; Shengsen Yang; Hao Wang; Jing Cui; Zhiyan Lu; Yuanye Lin; Yongyi Bi (Biological Trace Element Research, 2016)

Fine mapping of qKW7, a major QTL for kernel weight and kernel width in maize, confirmed by the combined analytic approaches of linkage and association analysis - Xin Li; Yong-xiang Li; Lin Chen; Xun Wu; Weiwei Qin; Yanchun Song; Dengfeng Zhang; Tianyu Wang; Yu Li; Yunsu Shi (Euphytica, 2016)

Effect of silicon on grain yield of rice under cadmium-stress - Hongmei Lin; Changxun Fang; Yingzhe Li; Weiwei Lin; Jianyu He; Ruiyu Lin; Wenxiong Lin (Acta Physiologiae Plantarum, 2016)

Metabolic activation of furan moiety makes Diosbulbin B hepatotoxic - Weiwei Li; Dongju Lin; Huiyuan Gao; Youjun Xu; Dongya Meng; Charles Vincent Smith; Ying Peng; Jiang Zheng (Archives of Toxicology, 2016)

CDK6 mediates the effect of attenuation of miR-1 on provoking cardiomyocyte hypertrophy - Weiwei Yuan; Chunmei Tang; Wensi Zhu; Jiening Zhu; Qiuxiong Lin; Yongheng Fu; Chunyu Deng; Yumei Xue; Min Yang; Shulin Wu; Zhixin Shan (Molecular and Cellular Biochemistry, 2016)

Permeability Imaging as a Biomarker of Leptomeningeal Collateral Flow in Patients with Intracranial Arterial Stenosis - Hui Chen; Bing Wu; Guangming Zhu; Max Wintermark; Xinhuai Wu; Zihua Su; Xiao Xu; Chenglin Tian; Lin Ma; Weiwei Zhang; Xin Lou (Cell Biochemistry and Biophysics, 2015)

Characterization of 14 microsatellite loci for the pan-oriental narrow-mouthed toad, Microhyla ornata (Amphibia: microhylidae) - Li Wei; Linmiao Li; Jinping Chen; Weiwei Shao; Zhihua Lin (Conservation Genetics Resources, 2015)

Taxonomy and molecular phylogeny of four Strombidium species, including description of S. pseudostylifer sp. nov. (Ciliophora, Oligotrichia) - Wen Song; Jiamei Li; Weiwei Liu; Khaled A. S. Al-rasheid; Xiaozhong Hu; Xiaofeng Lin (Systematics and Biodiversity, 2015)

The caspase-8 shRNA-modified mesenchymal stem cells improve the function of infarcted heart - Yeyou Liang; Qiuxiong Lin; Jiening Zhu; Xiaohong Li; Yongheng Fu; Xiao Zou; Xiaoying Liu; Honghong Tan; Chunyu Deng; Xiyong Yu; Zhixin Shan; Weiwei Yuan (Molecular and Cellular Biochemistry, 2014)

Universal DNA primers for amplification complete mitochondrial genome for sturgeons - Weiwei Shao; Li Wei; Linmiao Li; Hui Wang; Zhihua Lin; Jinping Chen (Conservation Genetics Resources, 2014)

Sustained endoplasmic reticulum stress inhibits hepatocyte proliferation via downregulation of c-Met expression - Yihuai He; Jun Long; Weiwei Zhong; Yu Fu; Ying Li; Shide Lin (Molecular and Cellular Biochemistry, 2014)

Synthesis and analgesic evaluation of a series of proline-typed spiro cyclic quaternary ammoniums - Songwen Lin; Na Wang; Shuo Zhao; Qi Sun; Weiwei Zhang; Jia Ye; Tieming Cheng; Runtao Li (Medicinal Chemistry Research, 2014)

A knockdown mutation of YELLOW-GREEN LEAF2 blocks chlorophyll biosynthesis in rice - Hong Chen; Zhijun Cheng; Xiaoding Ma; Han Wu; Yanling Liu; Kunneng Zhou; Yilin Chen; Weiwei Ma; Jingcui Bi; Xin Zhang; Xiuping Guo; Jiulin Wang; et al. (Plant Cell Reports, 2013)

Study on the Selectivity of Anion Receptors Based on Similar (thio)urea Fragments - Weiwei Huang; Zhongyue Yang; Hai Lin; Huakuan Lin (Journal of Fluorescence, 2013)

Interactive cellular proteins related to classical swine fever virus non-structure protein 2 by yeast two-hybrid analysis - Kai Kang; Kangkang Guo; Qinhai Tang; Yanming Zhang; Jiang Wu; Weiwei Li; Zhi Lin (Molecular Biology Reports, 2012)

Phylogeny of three choreotrich genera (Protozoa, Ciliophora, Spirotrichea), with morphological, morphogenetic and molecular investigations on three strobilidiid species - Weiwei Liu; Zhenzhen Yi; Xiaofeng Lin; Alan Warren; Weibo Song (Zoologica Scripta, 2012)
Liu, W., Yi, Z., Lin, X., Warren, A. & Song, W. (2012). Phylogeny of three choreotrich genera (Protozoa, Ciliophora, Spirotrichea), with morphological, morphogenetic and molecular investigations on three strobilidiid species. — Zoologica Scripta , 41 , 417–434. The phylogenetic relationships among three strobilidiid genera, namely Strobilidium , Rimostrombidium and Pelagostrobilidium , are investigated using a combination of morphological, morphogenetic and molecular data. The results indicate that all three genera belong to the same lineage, in which Rimostrombidium evolved first and Strobilidium and Pelagostrobilidium derived later. Improved genus diagnoses for Rimostrombidium and Pelagostrobilidium are supplied. The curved kinety 2 and the caudal spiralling of some somatic kineties are confirmed as generic characters for Pelagostrobilidium and Strobilidium , respectively. In addition, the morphology and morphogenesis of three species, namely R. veniliae ( Montagnes & Taylor, 1994 ) Petz et al., 1995 , P. paraepacrum sp. n. and P. minutum sp. n., isolated from the South China Sea are described. Pelagostrobilidium paraepacrum sp. n. is characterized by the presence of six somatic kineties, 30–32 external and two internal membranelles. Pelagostrobilidium minutum sp. n. is characterized by its extremely small body size, four somatic kineties, and in having one internal and 19–21 external membranelles. Rimostrombidium conicum Kahl, 1932 is transferred to the genus Pelagostrobilidium as P. conicum (Kahl, 1932) comb. nov.

Expression characteristics of two ubiquitin/ribosomal fusion protein genes in the developing testis, accessory gonad and ovary of Chinese mitten crab, Eriocheir sinensis - Qun Wang; Lili Chen; Ying Wang; Weiwei Li; Lin He; Hui Jiang (Molecular Biology Reports, 2012)

Reasons for lower transformation efficiency in indica rice using Agrobacterium tumefaciens-mediated transformation: lessons from transformation assays and genome-wide expression profiling - Weiwei Tie; Fei Zhou; Lei Wang; Weibo Xie; Hao Chen; Xianghua Li; Yongjun Lin (Plant Molecular Biology, 2012)

Taxonomy, morphology and molecular systematics of a new oligotrich ciliate, Williophrya maedai gen. nov., sp. nov., with redescriptions of Strombidium basimorphum and Pseudotontonia simplicidens (Protozoa, Ciliophora, Oligotrichia) - WEIWEI LIU; ZHENZHEN YI; ALAN WARREN; KHALED A. S. AL-RASHEID; SALEH A. AL-FARRAJ; XIAOFENG LIN; WEIBO SONG (Systematics and Biodiversity, 2011)

A Simple and Neutral Receptor Acting as a Sensitive and Switch-on Fluorescent Chemosensor for H2PO 4 − - Weiwei Huang; Hongyan Su; Sikai Yao; Hai Lin; Zunsheng Cai; Huakuan Lin (Journal of Fluorescence, 2011)

Cloning, characterization, expression, and copper sensitivity of the metallothionein-1 gene in the Chinese mitten crab, Eriocheir sinensis - Fei Ren; Hui Jiang; Jiangling Sun; Lin He; Weiwei Li; Ying Wang; Qun Wang (Molecular Biology Reports, 2011)

Characterization of the subcellular localization of herpes simplex virus type 1 proteins in living cells - Junji Xing; Shuai Wang; You Li; Hong Guo; Lei Zhao; Weiwei Pan; Fusen Lin; Huifang Zhu; Lei Wang; Meili Li; Lin Wang; Chunfu Zheng (Medical Microbiology and Immunology, 2011)

Functional analysis of a putative regulatory gene, tadR, involved in aniline degradation in Delftia tsuruhatensis AD9 - Lizhao Geng; Ming Chen; Quanfeng Liang; Wei Liu; Wei Zhang; Shuzhen Ping; Wei Lu; Yongliang Yan; Weiwei Wang; Masahiro Takeo; Min Lin (Archives of Microbiology, 2009)

Adult rat bone marrow stromal cells differentiate into Schwann cell-like cells in vitro - WeiWei Lin; Xue Chen; XiaoDong Wang; Jie Liu; XiaoSong Gu (In Vitro Cellular & Developmental Biology - Animal, 2008)